Nanoparticles of cerium oxide, dispersion, antiviral agent, antibacterial agent, resin composition, resin article, fiber material, fiber article, and method for producing nanoparticles of cerium oxide
By improving the preparation method of cerium oxide nanoparticles and utilizing specific stabilizers and hydrothermal treatment, the problem of poor colorability of nanoparticles was solved, resulting in a nanoparticle dispersion with low colorability and high activity, suitable for antibacterial agents, antiviral agents and related materials.
Patent Information
- Application Number
- CN202280065453.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-03-18
- Filing Date
- 2022-09-28
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-09-28
AI Technical Summary
The poor colorability of existing cerium oxide nanoparticle dispersions limits their application in antibacterial and antiviral agents, especially when combined with resins and fibers.
Cerium oxide nanoparticles were prepared by adding an oxidant to a solution containing basic amino acids, alicyclic amines, nitrogen-containing aromatic heterocyclic compounds, polymers with heterocyclic amine skeletons, or boron compounds, followed by hydrothermal treatment, thereby improving their colorability.
The prepared nanoparticle dispersion has low colorability, high antibacterial and antiviral activity, and is suitable for high-performance antiviral and antibacterial agents, and can also be used in resin and fiber materials.
Smart Images

Figure QLYQS_1 
Figure GDA0004761858060000051 
Figure GDA0004761858060000101
Abstract
Description
Technical Field
[0001] This invention relates to cerium oxide nanoparticles, dispersions containing nanoparticles, antiviral and antibacterial agents containing nanoparticles or dispersions, methods for manufacturing cerium oxide nanoparticles, and resin compositions, resin articles, fibrous materials, and fibrous articles containing cerium oxide nanoparticles. Background Technology
[0002] In recent years, with increased awareness of safety and hygiene management, antibacterial technologies that decompose harmful substances and microorganisms have attracted attention. For example, titanium dioxide possesses the property of oxidizing and decomposing organic matter through photocatalysis, and its performance is evaluated through the decomposition reaction of organic pigments. Besides its use as an antibacterial agent, this oxidative decomposition property also holds promise for applications in decomposing various harmful substances such as acetaldehyde, ammonia, allergens, and viruses.
[0003] On the other hand, cerium oxide nanoparticles (cerium nanoparticles) possess the same catalytic activity as oxidases such as oxidases and peroxidases, and are expected to be used as oxidants. Since these catalytic activities do not require special light sources such as ultraviolet light, their application in decomposing harmful substances can be expected even in situations where titanium oxide is difficult to use, such as indoors or in dark places.
[0004] In the manufacture of nanoparticles, a method is used to stabilize and disperse them by coexisting with stabilizers, thereby preventing the aggregation of nanoparticles. In the case of cerium oxide nanoparticles, for example, a particle dispersion is obtained by oxidizing cerium(III) ions with hydrogen peroxide using polyacrylic acid as a stabilizer, or by neutralizing cerium(III) ions with ammonia water using dextran as a stabilizer.
[0005] Here, Patent Document 1 discloses cerium oxide nanoparticles using amino acids as stabilizers. In particular, when lysine and arginine, which are basic amino acids, are used as stabilizers, the zeta potential of the nanoparticles increases. The cerium oxide nanoparticles obtained in this document are described as having a yellow color.
[0006] Furthermore, Patent Document 2 discloses cerium oxide nanoparticles using alicyclic amines as stabilizers. It describes how high oxidation performance is obtained by using piperazine and HEPES as stabilizers. It also describes that the cerium oxide nanoparticles obtained in this document are colored orange.
[0007] Patent document 3 discloses cerium oxide nanoparticles stabilized by aromatic heterocyclic compounds containing nitrogen atoms within their ring structures. It describes how high oxidation performance is achieved by using pyridine and imidazole as stabilizers. The document also describes that the cerium oxide nanoparticles obtained in this paper are colored orange.
[0008] Patent document 4 describes cerium oxide nanoparticles coated with a vinyl polymer or polyamide having a heterocyclic amine backbone. The document describes the cerium oxide content of these nanoparticles. 4+ It has a high specific gravity, and possesses oxidizing properties and antiviral activity. The cerium oxide nanoparticles obtained in this literature are described as having an orange color.
[0009] Furthermore, Patent Document 5 discloses a milling composition comprising colloidal cerium dioxide surface-modified with boric acid. It describes how the particles are stably dispersed over a wide pH range due to their negative charge. It also describes that the cerium oxide nanoparticles obtained in this document are colored orange.
[0010] Non-Patent Document 1 discloses cerium oxide nanoparticles stabilized with citric acid. It describes how the crystallinity of these particles is improved by heating at 50°C and hydrothermal treatment at 80°C. The cerium oxide nanoparticles obtained in this document are described as having a brown color.
[0011] Non-Patent Document 2 discloses cerium oxide nanoparticles stabilized with dextran. It describes that these particles possess antibacterial activity. It also describes that the cerium oxide nanoparticles obtained in this document are brown in color.
[0012] Existing technical documents
[0013] Non-patent literature
[0014] Non-patent literature 1: T. Masui et al., Journal of Materials Science Letters 2002, 21, 489.
[0015] Non-patent literature 2: E. Alpaslan et al., Scientific Reports 2017, 7:45859.
[0016] Patent documents
[0017] Patent Document 1: U.S. Patent Application Publication No. 2013 / 0273659
[0018] Patent Document 2: International Publication No. 2021 / 132643
[0019] Patent Document 3: International Publication No. 2021 / 132628
[0020] Patent Document 4: International Publication No. 2020 / 129963
[0021] Patent Document 5: Japanese Patent Application Publication No. 2003-183631 Summary of the Invention
[0022] The problem that the invention aims to solve
[0023] The inventors have conducted research to develop cerium oxide nanoparticles that can effectively decompose harmful substances and microorganisms. However, the cerium oxide nanoparticles described in Patent Documents 1-4, which contain lysine, HEPES, imidazole, and polyvinylimidazole as stabilizers, produce an orange-colored particle dispersion. Therefore, the nanoparticles manufactured based on these dispersions are limited in their application as antibacterial or antiviral agents, or in their composite with resins, fibers, or other substrates, thus requiring improved colorability. Even when using boric acid as a stabilizer as disclosed in Patent Document 5 and manufactured using the methods of Patent Documents 1-4, the orange color is not improved. Furthermore, the cerium oxide nanoparticles described in Non-Patent Documents 1 and 2, which contain citric acid and dextran as stabilizers, produce a brown-colored particle dispersion, similarly requiring improved colorability. Based on these results, further research was conducted to discover cerium oxide nanoparticles with excellent antibacterial and antiviral activity and low colorability.
[0024] Methods for solving problems
[0025] To address the aforementioned problems, the inventors conducted research focusing on the manufacturing process and stabilizers for cerium oxide nanoparticles. They discovered that by adding an oxidant to a solution containing a basic amino acid, alicyclic amine, an aromatic heterocyclic compound with a nitrogen atom within its ring structure, a polymer or boron compound having a heterocyclic amine backbone, and cerium(III) ions, and then subjecting the resulting solution to hydrothermal treatment, the colorability was improved. The resulting nanoparticles exhibited the following characteristics: maximum absorption was confirmed in the XANES spectrum in the range greater than 5729 eV and below 5731 eV and above 5735 eV and below 5739 eV, and Ce... 4+ With Ce 3+ The molar ratio is 40:60 to 100:0. Furthermore, it also exhibits the following characteristics: in the XRD spectrum, it has diffraction peaks at Bragg angles (2θ) of 27°–29°, 31°–33°, 46°–48°, and 55°–57°, with the peak intensity at 27°–29° being less than 1.8 compared to the peak intensity at 46°–48°. It was also found that the nanoparticles, when prepared as a dispersion, possess a positive Zeta potential and exhibit high antibacterial and antiviral activity, thus completing this invention.
[0026] The present invention is described below.
[0027] (1) A cerium oxide nanoparticle, characterized in that it is a cerium oxide nanoparticle containing a basic amino acid, an alicyclic amine, an aromatic heterocyclic compound containing a nitrogen atom in the ring structure, a polymer having a heterocyclic amine skeleton, or a boron compound as a stabilizer, wherein the APHA of a 1% by mass dispersion is less than 400.
[0028] (2) The cerium oxide nanoparticles according to (1) have a zeta potential of +10mV or higher at pH 7.
[0029] (3) Cerium oxide nanoparticles according to (1) or (2), wherein Ce 4+ With Ce 3+ The molar ratio is 40:60 to 100:0.
[0030] (4) A type of cerium oxide nanoparticle, comprising a basic amino acid, an alicyclic amine, an aromatic heterocyclic compound containing a nitrogen atom within its ring structure, a polymer having a heterocyclic amine backbone, or a boron compound as a stabilizer, exhibiting maximum absorption in the Ce L3-terminal XANES spectrum obtained by X-ray absorption fine structure spectroscopy in the range greater than 5729 eV and less than 5731 eV and in the range greater than 5735 eV and less than 5739 eV, and Ce… 4+ With Ce 3+ The molar ratio is 40:60 to 100:0.
[0031] (5) A cerium oxide nanoparticle, comprising a basic amino acid, an alicyclic amine, an aromatic heterocyclic compound containing a nitrogen atom in the ring structure, a polymer having a heterocyclic amine skeleton, or a boron compound as a stabilizer, having diffraction peaks at Bragg angles (2θ) of 27°–29°, 31°–33°, 46°–48°, and 55°–57° in XRD spectra, wherein the ratio of the peak intensity at 27°–29° to the peak intensity at 46°–48° is less than 1.8.
[0032] (6) The cerium oxide nanoparticles according to any one of (1) to (5), wherein the above-mentioned alicyclic amine is an alicyclic amine represented by the following general formula (I).
[0033]
[0034] (In equation (I), X represents NR) 2 O, S, R 1 and R 2 R represents hydrogen atoms, alkyl groups with 1 to 4 carbon atoms, hydroxyalkyl groups with 1 to 4 carbon atoms, aminoalkyl groups with 1 to 4 carbon atoms, and sulfonic acid alkyl groups with 1 to 4 carbon atoms. 1 and R 2They can be the same or different.
[0035] (7) The cerium oxide nanoparticles according to any one of (1) to (5), wherein the aromatic heterocyclic compound containing nitrogen atoms in the ring structure does not have substituents, or has at least one substituent selected from methyl, ethyl, amino, aminomethyl, monomethylamino, dimethylamino, and cyano, and is an aromatic heterocyclic compound containing 2 to 8 carbon atoms and 1 to 4 nitrogen atoms in the ring structure.
[0036] (8) The cerium oxide nanoparticles according to any one of (1) to (5), wherein the polymer having a heterocyclic amine backbone is a vinyl polymer or polyamide having a heterocyclic amine backbone.
[0037] (9) The cerium oxide nanoparticles according to any one of (1) to (5), wherein the boron compound is a boron compound represented by the following general formula (II).
[0038] BR n (OR') 3-n (II)
[0039] (In formula (II), n is an integer from 0 to 2, R represents any one of alkyl, phenyl, or tolyl groups having 1 to 4 carbon atoms, and R' represents any one of hydrogen, alkyl, phenyl, or tolyl groups having 1 to 4 carbon atoms. When multiple R or R' exist, they can be the same or different.)
[0040] (10) The cerium oxide particles according to any one of (1) to (9) are characterized in that the particle size is 1 to 300 nm.
[0041] (11) A dispersion comprising cerium oxide nanoparticles as described in any one of (1) to (10).
[0042] (12) An antiviral agent comprising cerium oxide nanoparticles as described in any one of (1) to (10) or a dispersion as described in (11).
[0043] (13) An antibacterial agent comprising cerium oxide nanoparticles as described in any one of (1) to (10) or a dispersion as described in (11).
[0044] (14) A resin composition comprising cerium oxide nanoparticles as described in any one of (1) to (10).
[0045] (15) A resin article wherein the resin composition described in (14) is used.
[0046] (16) The resin product according to (15) is selected from automotive interior materials, electrical product housings, hanging handles, armrests, door handles, and partitions.
[0047] (17) A fiber material comprising cerium oxide nanoparticles as described in any one of (1) to (10).
[0048] (18) The fiber material according to (17) is characterized in that it has a water pressure resistance of 500 mmH2O or higher.
[0049] (19) A fiber article wherein the fiber material described in (17) or (18) is used.
[0050] (20) The fiber products according to (18) are selected from masks, protective clothing, filters, mats, chairs, burqas, white coats, curtains, bed sheets, automotive interior materials, and rags.
[0051] (21) A method for manufacturing cerium oxide nanoparticles, comprising the following steps:
[0052] Step a) is the process of adding an oxidizing agent to a solution containing basic amino acids, alicyclic amines, aromatic heterocyclic compounds containing nitrogen atoms in their ring structure, polymers having a heterocyclic amine backbone, or boron compounds and containing cerium(III) ions.
[0053] Step b) is a process of hydrothermal treatment of the solution obtained in step a).
[0054] (22) According to the method described in (21), the APHA of the 1% mass dispersion of the above-mentioned cerium oxide nanoparticles is 400 or less.
[0055] The effects of the invention
[0056] The cerium oxide nanoparticles and dispersions containing these nanoparticles of the present invention exhibit lower colorfastness compared to conventional cerium oxide nanoparticles. Furthermore, the cerium oxide nanoparticles and dispersions containing these nanoparticles of the present invention demonstrate excellent antibacterial and antiviral activity, and can be used as high-performance antiviral and antibacterial agents for inactivating viruses and bacteria. Additionally, resin compositions and fiber materials containing the cerium oxide nanoparticles of the present invention exhibit lower colorfastness compared to conventional resin compositions and fiber materials containing cerium oxide nanoparticles. Attached Figure Description
[0057] Figure 1 A diagram illustrating the structure of the polymer used in this invention.
[0058] Figure 2 A diagram illustrating the structure of the polymer with a piperazine backbone used in this invention.
[0059] Figure 3 This is a graph showing the CeL3-terminal XANES spectra of cerium oxide nanoparticles produced in Example 1 and Comparative Example 1, which were measured in Example 11 and Comparative Example 10.
[0060] Figure 4 This is a graph showing the CeL3-terminal XANES spectra of cerium oxide nanoparticles produced in Example 2 and Comparative Example 2, which were measured in Example 11 and Comparative Example 10.
[0061] Figure 5 This is a graph showing the CeL3-terminal XANES spectra of cerium oxide nanoparticles produced in Example 3 and Comparative Example 3, which were measured in Example 11 and Comparative Example 10.
[0062] Figure 6 This is a graph showing the CeL3-terminal XANES spectra of cerium oxide nanoparticles produced in Example 4 and Comparative Example 4, which were measured in Example 11 and Comparative Example 10.
[0063] Figure 7 This is a graph showing the CeL3-terminal XANES spectra of cerium oxide nanoparticles produced in Example 5 and Comparative Example 5, which were measured in Example 11 and Comparative Example 10.
[0064] Figure 8 This is a graph showing the XRD spectrum of the cerium oxide nanoparticles produced in Example 1, which was measured in Example 13.
[0065] Figure 9 This is a graph showing the XRD spectrum of the cerium oxide nanoparticles produced in Example 2, which was measured in Example 13.
[0066] Figure 10 This is a graph showing the XRD spectrum of the cerium oxide nanoparticles produced in Example 3, which was measured in Example 13.
[0067] Figure 11 This is a graph showing the XRD spectrum of the cerium oxide nanoparticles produced in Example 4, which was measured in Example 13.
[0068] Figure 12 This is a graph showing the XRD spectrum of the cerium oxide nanoparticles produced in Example 5, which was measured in Example 13.
[0069] Figure 13 The image shows the XRD spectrum of the cerium oxide nanoparticles produced in Comparative Example 1, which was measured in Comparative Example 12.
[0070] Figure 14 The image shows the XRD spectrum of the cerium oxide nanoparticles produced in Comparative Example 2, which was measured in Comparative Example 12.
[0071] Figure 15 The image shows the XRD spectrum of the cerium oxide nanoparticles produced in Comparative Example 3, which was measured in Comparative Example 12.
[0072] Figure 16 The image shows the XRD spectrum of cerium oxide nanoparticles produced in Comparative Example 4, which was measured in Comparative Example 12.
[0073] Figure 17 The image shows the XRD spectrum of the cerium oxide nanoparticles produced in Comparative Example 5, which was measured in Comparative Example 12.
[0074] Figure 18 The image shows the XRD spectrum of cerium oxide nanoparticles produced in Comparative Example 6, which was measured in Comparative Example 12.
[0075] Figure 19 The image shows the XRD spectrum of the cerium oxide nanoparticles produced in Comparative Example 7, which was measured in Comparative Example 12.
[0076] Figure 20 This is a graph showing the XRD spectrum of cerium oxide nanoparticles produced in Reference Example 1, which was measured in Comparative Example 12. Detailed Implementation
[0077] The cerium oxide nanoparticles of the present invention are sometimes referred to simply as the nanoparticles of the present invention in this specification. In addition, the dispersion containing the cerium oxide nanoparticles of the present invention is sometimes referred to simply as the dispersion of the present invention in this specification.
[0078] [Cerium oxide nanoparticles]
[0079] The nanoparticles of the present invention are characterized by low coloring properties when formed into a dispersion. Previously known cerium oxide nanoparticles, when formed into a dispersion, are colored yellow, orange, red, brown, etc., but the dispersion containing the nanoparticles of the present invention is transparent or a very light yellow.
[0080] A 1% by mass dispersion of the nanoparticles of the present invention showed a value below 400 when evaluated by the Hassen colorimetric assay (APHA). APHA is known as an indicator that can highly sensitively evaluate substances causing unknown coloration.
[0081] In a dispersion of cerium oxide nanoparticles adjusted to 1% by mass, the range of APHA is as long as it is below 400, preferably below 300, more preferably below 250, and most preferably below 200, in order to improve the coloring range.
[0082] The APHA test shall be performed according to the method specified in JIS, or using a commercially available testing apparatus. For example, the OME2000 from Nippon Denshoku Kogyo Co., Ltd. can be used for APHA testing.
[0083] APHA determination is performed using a dispersion containing nanoparticles. The particle concentration is adjusted to 1% by mass, the pH is adjusted to 2–12, and the measurement is conducted at 25°C. For low particle concentrations, membrane concentration or evaporation is performed; for high particle concentrations, dilution with a solvent is used to adjust the concentration. When the particle concentration of the dispersion is known, the concentration can be adjusted using the above methods. If the cerium oxide concentration is unknown, for example, the cerium ion concentration can be determined by ICP emission spectrometry (ICP-OES) or ICP mass spectrometry (ICP-MS), assuming that all cerium ions are CeO2, and the concentration can be adjusted accordingly. If the nanoparticles are a dispersion and do not contain impurities that affect the APHA value, the APHA of the dispersion can be determined using the APHA of only the solvent constituting the dispersion (e.g., water) as a reference. If the dispersion contains compounds other than the cerium oxide nanoparticles that affect the APHA value, these can be removed by membrane purification or similar methods before measurement. When it is difficult to remove compounds that affect the APHA value, the solution containing the compound can be used as a reference for determination, and the APHA can be determined by difference. If debris is present in addition to cerium oxide, the debris can be removed by centrifugation, and the supernatant can be measured. Alternatively, the dispersion can be ultrasonically treated before measurement.
[0084] Furthermore, when the nanoparticles are in powder form, they are redispersed in a solvent for determination. Solvents selected include hexane, ethyl acetate, chloroform, methanol, ethanol, DMSO, water, or mixtures thereof. Water is preferred, but to improve dispersibility, the pH can be adjusted, or a mixture of water and organic solvents such as methanol, ethanol, or DMSO, which are compatible with water, can be used. When using a mixed solvent, the mixing ratio can be water:organic solvent = 1:99 to 99:1. Hexane, ethyl acetate, or chloroform can also be used when the nanoparticles have low dispersibility in polar solvents. Heating / cooling or ultrasonic treatment can also be performed to promote dispersion.
[0085] The manufacture of cerium oxide nanoparticles of the present invention uses water-soluble cerium salts as one of the raw materials, and is carried out with water or a solvent compatible with water.
[0086] The stabilizer used in this invention is a compound with moderate hydrophilicity and the property of forming crystal nuclei for nanoparticles by forming complexes with metal ions or coordinating with hydroxyl groups, or of stably dispersing the formed nanoparticles. As the stabilizer used in this invention, basic amino acids (A), alicyclic amines (B), aromatic heterocyclic compounds containing nitrogen atoms in their ring structure (C), polymers having a heterocyclic amine backbone (D), or boron compounds (E) are used.
[0087] (A) Basic amino acids
[0088] Basic amino acids (A) used as stabilizers include, specifically, lysine, arginine, histidine, and tryptophan. They can be any optical isomer of the D-type or L-type isomers, or mixtures thereof.
[0089] (B) Alicyclic amines
[0090] Alicyclic amines (B) used as stabilizers include alicyclic amines represented by chemical formula (I).
[0091]
[0092] In equation (I), X represents NR. 2 O, S, R 1 and R 2 R represents hydrogen atoms, alkyl groups with 1 to 4 carbon atoms, hydroxyalkyl groups with 1 to 4 carbon atoms, aminoalkyl groups with 1 to 4 carbon atoms, and sulfonic acid alkyl groups with 1 to 4 carbon atoms. 1 and R 2 They can be the same or different.
[0093] In a more preferred embodiment of the alicyclic amine (B) used as a stabilizer, in the above chemical formula (I), X represents NR. 2 O, R 1 and R 2 R represents hydrogen atoms, alkyl groups with 1 to 2 carbon atoms, hydroxyalkyl groups with 2 to 3 carbon atoms, aminoalkyl groups with 2 to 3 carbon atoms, and sulfonic acid alkyl groups with 2 to 3 carbon atoms. 1 and R 2 They can be the same or different.
[0094] As one embodiment, examples of such alicyclic amines (B) include piperazine, 1-methylpiperazine, N,N'-dimethylpiperazine, 1-ethylpiperazine, N,N'-diethylpiperazine, 1-(2-hydroxyethyl)piperazine, 1,4-bis(2-hydroxyethyl)piperazine, N-(2-aminoethyl)piperazine, 1,4-bis(2-aminoethyl)piperazine, 2-[4-(2-hydroxyethyl)-1-piperazinyl]ethanesulfonic acid, piperazine-1,4-bis(2-ethanesulfonic acid), morpholine, 4-methylmorpholine, 4-ethylmorpholine, 4-(2-aminoethyl)morpholine, 4-(2-hydroxyethyl)morpholine, 2-morpholinoethanesulfonic acid, and 3-morpholinopropanesulfonic acid.
[0095] (C) Aromatic heterocyclic compounds
[0096] Examples of aromatic heterocyclic compounds (C) containing nitrogen atoms within their ring structure as stabilizers include those containing 2 to 8 carbon atoms and 1 to 4 nitrogen atoms within their ring structure. Furthermore, at least one of the nitrogen atoms preferably has a lone pair of electrons not included in the π-conjugated system. As a more preferred embodiment of the aromatic heterocyclic compound used in this invention, in addition to the above features, monocyclic or bicyclic compounds having 5-membered or 6-membered ring structures are also included. Examples of such aromatic heterocyclic compounds include pyrazoles, imidazoles, triazoles, pyridines, pyridazines, pyrimidines, pyrazines, triazines, tetrazines, indazoles, benzimidazoles, azaindole, pyrazolopyrimidines, purines, benzotriazoles, quinoxalines, cyclophosphines, quinazolines, phthalazines, naphthidines, and pteridines. Furthermore, the aforementioned aromatic heterocyclic compounds can be derivatives of compounds that form complexes and have substituents such as methyl, ethyl, amino, aminomethyl, monomethylamino, dimethylamino, and cyano, which do not significantly change the solubility in the reaction solvent.
[0097] (D) Polymers with a heterocyclic amine backbone
[0098] Examples of polymers (D) with a heterocyclic amine backbone used as stabilizers include vinyl polymers or polyamides with a heterocyclic amine backbone.
[0099] A more preferred embodiment of the polymer (D) having a heterocyclic amine backbone as a stabilizer is, for example... Figure 1 As shown, in the main chain ( Figure 1 (a)) or sidechain ( Figure 1 (b) and (c)) have a heterocyclic amine skeleton R such as piperazine, pyridine, imidazole or carbazole. The vinyl polymers or polyamides of the present invention may have substituents at any position of the main chain or side chain, and may also have substituents at any position of the heterocyclic amine skeleton such as piperazine, pyridine, imidazole or carbazole. Figure 1The polymer shown in (a) has a heterocyclic amine backbone in the main chain and substituents R in the side chains. 3 and R 4 . Figure 1 (b) The polymer shown has a heterocyclic amine backbone in its side chain, and the substituents serving as the heterocyclic amine backbone have substituent R. 4 . Figure 1 (c) The polymer shown has a heterocyclic amine backbone in its side chain, where the heterocyclic amine backbone is a substituent R in the side chain. 3 The substituents, as substituents of the heterocyclic amine skeleton, have substituent R. 5 . Figure 1 The structures shown in (a) to (c) are examples of vinyl polymers or polyamides used as stabilizers, and are not limited thereto. Furthermore, unless otherwise specified in this specification, the substituents are alkyl, acetyl, hydroxyl, amino, cyano, carboxyl, ester, aldehyde, amide, ether, ketone, halogen, sulfonic acid, or phosphate groups. The number of substituents can be single or multiple.
[0100] Vinyl polymers used as stabilizers are polymers with methylene groups in their main chain. As an example, the structure of a vinyl polymer with a piperazine backbone in its main chain or side chains is shown below. Figure 2 In (a) and (b), for example... Figure 2 As shown in (a), when the main chain has a piperazine skeleton, a piperazine skeleton is present between the methylene groups in the main chain. The same applies when the main chain has other heterocyclic amine skeletons such as pyridine, imidazole, or carbazole. Figure 2 (a) Similarly, there is a heterocyclic amine skeleton between the methylene groups.
[0101] In the case where the side chains of vinyl polymers have a piperazine backbone, such as Figure 2 As shown in (b), the piperazine skeleton can be directly bonded to the carbon atom of the methylene group, or it can be bonded via an alkyl or amino group. In the case of other heterocyclic amine skeletons such as pyridine, imidazole, or carbazole, it can bond with... Figure 2 (b) Similarly, heterocyclic amine skeletons such as pyridine, imidazole or carbazole skeletons can be directly bonded to the carbon of methylene or via alkyl or amino groups.
[0102] Vinyl polymers are preferably vinyl polymers having a piperazine, pyridine, imidazole, or carbazole backbone in the side chain. Vinyl polymers having a piperazine, pyridine, imidazole, or carbazole backbone in the side chain are obtained by polymerization of vinyl monomers having vinyl groups.
[0103] Specific examples of vinyl monomers include 1-vinylpiperazine, (4-vinylpiperazin-1-yl)methaneamine, 2-(4-vinylpiperazin-1-yl)ethane-1-amine, 2-vinylpiperazine, (3-vinylpiperazin-1-yl)methaneamine, 2-(3-vinylpiperazin-1-yl)ethane-1-amine, (2-vinylpiperazin-1-yl)methaneamine, 2-vinylpyridine, 3-vinylpyridine, 4-vinylpyridine, 1-vinylimidazole, 2-vinylimidazole, 4-vinylimidazole, and 9-vinylcarbazole. Furthermore, the above-mentioned vinyl monomers may have substituents at any position other than the vinyl group, and may also have methyl or cyano groups as substituents in the vinyl group.
[0104] Vinyl polymers can be homopolymers or copolymers made from two or more vinyl monomers.
[0105] Preferred examples of vinyl polymers used in this invention are poly(1-vinylpiperazine), poly((4-vinylpiperazine-1-yl)methaneamine), poly(2-(4-vinylpiperazine-1-yl)ethane-1-amine), poly(2-vinylpyridine), poly(3-vinylpyridine), poly(4-vinylpyridine), poly(1-vinylimidazolium), poly(2-vinylimidazolium), poly(4-vinylimidazolium), and poly(9-vinylcarbazole).
[0106] Polyamides are polymers with amide bonds in their main chain. For example... Figure 2 As shown in (c), when the main chain has a piperazine skeleton, a piperazine skeleton exists between the carbonyl groups in the main chain, and the nitrogen in the heterocycle of the piperazine skeleton forms an amide bond with the carbonyl group. When the main chain has other heterocyclic amine skeletons with two or more primary or secondary amino groups, such as pyridine, imidazole, or carbazole skeletons, it also... Figure 2 (c) Similarly, there is a heterocyclic amine skeleton between the carbonyl groups.
[0107] In the case of polyamides having a piperazine backbone, such as Figure 2 As shown in (d), the piperazine skeleton can be directly bonded to the carbon atom linking the amide group, or it can be bonded via an alkyl or amino group. In the case of other heterocyclic amine skeletons such as pyridine, imidazole, or carbazole skeletons, it can be combined with... Figure 2 (d) Similarly, heterocyclic amine skeletons such as pyridine, imidazole or carbazole skeletons can be directly bonded to the carbon atom linked to the amide group, or they can be bonded via alkyl or amino groups.
[0108] Polyamides are preferably polymers with a piperazine backbone in the main chain or side chains, and more preferably... Figure 2 (c) shows a polymer with a piperazine backbone in its main chain.
[0109] Polyamides with a piperazine backbone in their main chain are obtained by polycondensation of an amine with a piperazine backbone and a dicarboxylic acid.
[0110] Preferred examples of amines having a piperazine skeleton include piperazine, (aminomethyl)piperazine, (aminoethyl)piperazine, (aminopropyl)piperazine, (aminobutyl)piperazine, 1,4-bis(aminomethyl)piperazine, 1,4-bis(2-aminoethyl)piperazine, 1,4-bis(3-aminopropyl)piperazine, and 1,4-bis(4-aminobutyl)piperazine. Among these, (aminoethyl)piperazine and 1,4-bis(3-aminopropyl)piperazine are more preferred. Furthermore, these amines may have substituents at any position except for the nitrogen atom capable of forming an amide bond.
[0111] Preferred examples of dicarboxylic acids include 1H-imidazolium-2,4-dicarboxylic acid, 1H-imidazolium-2,5-dicarboxylic acid, 1H-imidazolium-4,5-dicarboxylic acid, pyridine-2,3-dicarboxylic acid, pyridine-2,4-dicarboxylic acid, pyridine-2,5-dicarboxylic acid, pyridine-2,6-dicarboxylic acid, pyridine-3,4-dicarboxylic acid, pyridine-3,5-dicarboxylic acid, adipic acid, sebacic acid, dodecanoic acid, terephthalic acid, and isophthalic acid. Furthermore, these dicarboxylic acids may have substituents at any position except for the carboxyl group capable of forming an amide bond.
[0112] Polyamides obtained by combining the above-mentioned amines with dicarboxylic acids are preferred for use, and polyamides obtained by combining (aminoethyl)piperazine with adipic acid are particularly preferred.
[0113] Furthermore, polyamides can have a structure with polyalkylene glycols in the main chain. Specifically, examples include polyamides having a backbone of (aminoethyl)piperazine, adipic acid, and bis(aminopropyl)polyethylene glycol.
[0114] In addition, polyamides can be polyamides with heterocyclic amine backbones such as piperazine, pyridine, imidazole or carbazole, mixtures with other polymers, or copolymers. In this case, specific examples of other polymers include polyhexamethylene adipamide (Nylon 6), polyhexamethylene adipamide (Nylon 66), polybutadiene adipamide (Nylon 46), polypentyl adipamide (Nylon 56), polypentyl decanteramide (Nylon 510), polyhexamethylene decanteramide (Nylon 610), polyhexamethylene dodecyl diamide (Nylon 612), polyhexamethylene adipamide / polyhexamethylene terephthalamide copolymer (Nylon 66 / 6T), polyhexamethylene adipamide / polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (Nylon 66 / 6T / 6I), polyhexamethylene terephthalamide / polyhexamethylene isophthalamide copolymer (Nylon 6T / 6I), and polydimethyl adipamide (Nylon XD6).
[0115] The vinyl polymers and polyamides used in this invention have a molecular weight of 3,000 or more and 1,000,000 or less, preferably 10,000 or more and 50,000 or less.
[0116] (E) Boron compounds
[0117] Boron compounds used as stabilizers include those represented by chemical formula (II).
[0118] BR n (OR') 3-n (II)
[0119] In formula (II), n is an integer from 0 to 2, R represents any one of alkyl, phenyl, or tolyl groups having 1 to 4 carbon atoms, and R' represents any one of hydrogen, alkyl, phenyl, or tolyl groups having 1 to 4 carbon atoms. Multiple R or R' groups may exist, and each may be the same or different. The tolyl group may be any one of ortho-tolyl, meta-tolyl, or para-tolyl. When multiple tolyl groups exist, each may be the same or different.
[0120] As a more preferred embodiment of the boron compound used in this invention, examples include boric acid (in general formula (II), n = 0, R = H, R' = H), borate esters (in general formula (II), n = 0, R = H, R' = alkyl, etc.), monosubstituted boric acid (in general formula (II), n = 1, R = alkyl, etc., R' = H), monosubstituted borate esters (in general formula (II), n = 1, R = alkyl, etc., R' = alkyl, etc.), disubstituted boric acid (in general formula (II), n = 2, R = alkyl, etc., R' = H), disubstituted borate esters (in general formula (II), n = 2, R = alkyl, etc., R' = alkyl, etc.), and borates. In this invention, borates refer to salts containing boric acid, or salts of metaboric acid, polyboric acid, etc., formed by the dehydration condensation of boric acid. These borates obtain the structure of boric acid as shown in general formula (II) in solution because they achieve an equilibrium state between boric acid and tetrahydroxyboric acid in aqueous solution. The counterion of boric acid in borates can be any ion such as lithium ion, sodium ion, potassium ion, ammonium ion, etc.
[0121] Examples of such boron compounds include boric acid; borate esters such as trimethyl borate, triethyl borate, tripropyl borate, triisopropyl borate, tributyl borate, and triisobutyl borate; and monosubstituted boric acids such as methylboric acid, ethylboric acid, propylboric acid, isopropylboric acid, butylboric acid, isobutylboric acid, and phenylboric acid. Furthermore, examples of borates include lithium, sodium, potassium, and ammonium salts of boric acid, metaboric acid, diboric acid, tetraboric acid, pentaboric acid, hexaboric acid, and octaboric acid.
[0122] The cerium oxide nanoparticles involved in this invention preferably contain 0.001 to 10 moles of boron per mole of cerium. More preferably, they are in the range of 0.001 to 1 mole.
[0123] In this invention, the cerium oxide nanoparticles are composed of a mixture of Ce₂O₃ and CeO₂. In addition to the aforementioned oxide forms, cerium oxide can also contain forms as hydroxides and hydroxyl oxides. The ratio of Ce₂O₃ to CeO₂ can be calculated as the ratio of cerium(III) to cerium(IV) using X-ray photoelectron spectroscopy (XPS) or similar methods described later.
[0124] The cerium oxide nanoparticles of the present invention may further include transition metals from groups 3 to 12 of the periodic table. It is expected that these metals will improve performance by acquiring valences of 2+ to 3+, thereby forming lattice defects when doped into cerium oxide nanoparticles, or by causing valence changes in cerium oxide due to valence changes associated with redox potentials such as 0 and 1+, 1+ and 2+, 2+ and 3+.
[0125] From the viewpoint that nanoparticles can be easily doped with cerium oxide to further enhance their antibacterial and antiviral activities, these transition metals are preferably transition metals from periods 4 to 6, and more preferably Ti, Mn, Fe, Co, Ni, Cu, Zn, Zr, and Ag.
[0126] These transition metals, in addition to organic acid salts such as carboxylates and sulfonates, oxyphosphates such as phosphates and phosphonates, and inorganic acid salts such as nitrates, sulfates, and carbonates, can also be added during manufacturing as salts of halides and hydroxides. They only need to be dissolved in the solvent used during manufacturing.
[0127] [Methods for manufacturing cerium oxide nanoparticles]
[0128] The dispersion of cerium oxide nanoparticles containing the present invention is manufactured by adding an oxidant to a solution containing a stabilizer and cerium(III) ions, and then subjecting the mixture to hydrothermal treatment. The method for manufacturing the dispersion of cerium oxide nanoparticles of the present invention will be described below.
[0129] (1) First process
[0130] The first step is to obtain a solution containing a stabilizer and cerium(III) ions. The stabilizer-containing solution used in this step can be prepared by dissolving the stabilizer in any solvent. The solvent is preferably water or a solvent compatible with water. Specific examples of solvents compatible with water include methanol, ethanol, propanol, isopropanol, butanol, tert-butanol, tetrahydrofuran, acetone, dimethylformamide (DMF), dimethyl sulfoxide (DMSO), glycerol, ethylene glycol, and oligomeric polyethylene glycol. The mixing ratio of the solvent and water can be set to any concentration from 10% to 90% by mass. If the stabilizer is not easily soluble in the solvent, it can be dissolved by heating or ultrasonic treatment.
[0131] When using a polymer (D) having a heterocyclic amine backbone as a stabilizer, the concentration of the polymer (D) solution can be 0.001% or more and 50% or less by mass concentration, preferably 0.01% or more and 5% or less, more preferably 0.1% or more and 2% or less.
[0132] When using basic amino acid (A) as a stabilizer, the amount of basic amino acid (A) can be in the range of 0.01 to 10 molar equivalents relative to cerium (III) ions.
[0133] The amount of alicyclic amine (B) used as a stabilizer can be in the range of 0.1 to 100 molar equivalents relative to cerium (III) ions.
[0134] When using an aromatic heterocyclic compound (C) containing nitrogen atoms in its ring structure as a stabilizer, the amount of the aromatic heterocyclic compound (C) containing nitrogen atoms in its ring structure can be in the range of 0.1 to 100 molar equivalents relative to cerium (III) ions.
[0135] When using a polymer (D) having a heterocyclic amine backbone as a stabilizer, and using cerium(III) nitrate hexahydrate as a cerium(III) salt, the mixture can be prepared such that the mass ratio of cerium(III) nitrate hexahydrate to polymer (D) is 0.1 or more and 5.0 or less.
[0136] When using boron compound (E) as a stabilizer, the amount of boron compound (E) can be in the range of 0.1 to 1000 molar equivalents relative to cerium (III) ions, preferably 1 to 200 molar equivalents, more preferably 5 to 200 molar equivalents, and most preferably 10 to 100 molar equivalents.
[0137] To obtain a solution containing a stabilizer and cerium(III) ions, a solution containing the stabilizer can be prepared separately and then mixed with a solution containing cerium(III) ions. If the solvent of the solution containing the stabilizer is water or a solvent compatible with water, a cerium(III) salt can be added to the solution containing the stabilizer and then mixed.
[0138] Solutions containing cerium(III) ions can be prepared simply by dissolving a cerium(III) salt in any solvent. For example, cerium(III) nitrate hexahydrate can be used as a cerium(III) salt.
[0139] Regarding the amount of cerium(III) salt, it can be mixed with the stabilizer solution in such a way that the final concentration of the reaction solution is in the range of 0.01% to 10% by mass. The mixed solution is preferably mixed for at least 5 minutes until the solution becomes homogeneous.
[0140] When the cerium oxide nanoparticles of the present invention are doped with metal using boron compound (E) as a stabilizer, a transition metal can be further added in the first step. The transition metal can be added directly as a metal salt in solid state to a solution containing boron compound (E) and cerium (III) ions or cerium (III) salt, or a solution prepared by dissolving the metal salt in any solvent can be added to the solution containing boron compound (E) and cerium (III) ions or cerium (III) salt.
[0141] The amount of transition metal is preferably in the range of 0.0001 mol to 0.3 mol relative to 1 mol of cerium(III) ions. More preferably, it is in the range of 0.001 mol to 0.2 mol. In addition, the amount of transition metal does not include the amount of elements other than transition metal contained in the salt of the transition metal.
[0142] (2) Second process
[0143] The second step is the addition of an oxidizing agent to the mixed solution obtained in the first step. Examples of oxidizing agents used in the second step include nitric acid, potassium nitrate, hypochlorous acid, chlorite, chloric acid, perchloric acid, halogens, permanganates, chromic acid, dichromic acid, oxalic acid, sulfur dioxide, sodium thiosulfate, sulfuric acid, and hydrogen peroxide. Hydrogen peroxide is particularly preferred. The amount of oxidizing agent added can be 0.1 equivalents or more and 10 equivalents or less relative to cerium(III) ions, preferably 0.5 equivalents or more and 2 equivalents or less.
[0144] If an oxidizing agent is added to a solution containing a stabilizer and cerium(III) ions, the cerium(III) ions are oxidized to cerium(IV), initiating the formation reaction of cerium oxide particles, which are composed of a mixture of Ce₂O₃ and CeO₂. Furthermore, during this reaction, the solution is colored yellow, orange, red, brown, etc. The end of the reaction can be determined by the point where the color no longer changes.
[0145] The formation reaction of cerium oxide nanoparticles can be carried out at any pH, but considering that the reaction is easier to carry out under weakly acidic to alkaline conditions, the pH of the solution when the oxidant is added is preferably set to 5 or higher beforehand, more preferably to 6 or higher beforehand, and even more preferably to 7 or higher beforehand. Sodium hydroxide aqueous solution, ammonia aqueous solution, etc., can be used when adjusting the pH. The reaction usually ends in about 5 minutes to 1 hour, obtaining a dispersion containing the cerium oxide nanoparticles of the present invention. For example, if 1 ml of a 10% by mass aqueous solution of cerium(III) nitrate hexahydrate is added to a 284 mg / 50 ml aqueous solution of boric acid adjusted to pH 8, and then 1 ml of a 1.2% by mass aqueous solution of hydrogen peroxide is added and stirred at room temperature, the solution turns orange and the particle formation reaction ends in about 10 minutes, obtaining the dispersion of the present invention.
[0146] The formation reaction of cerium oxide nanoparticles can be carried out at any temperature from 4°C to 100°C. When proceeding with cooling, a cold bath such as the BBL101 from Yamato Scientific Co., Ltd. can be used; when proceeding with heating, a hot bath such as the OHB-1100S from Tokyo Rika Machine Co., Ltd. can be used. In either case, simply add the reaction solution to a glass container and stir while cooling, heating, or refluxing.
[0147] The pH of the mixture after adding an oxidant can be adjusted. pH adjustment improves particle dispersibility. The pH of the mixture only needs to be in the range of pH 1 to 10, preferably pH 2 to 8. The pH can be adjusted by adding a buffer solution, or by adding acids such as nitric acid, sulfuric acid, or hydrochloric acid, or bases such as sodium hydroxide or potassium hydroxide. Furthermore, the pH of the dispersion can be adjusted after purification of the dispersion, such as by ultrafiltration or dialysis using a semi-permeable membrane, as described later.
[0148] The dispersion obtained in the second process can be used directly in the third process, or it can be used as a dispersion that has been dried, powdered, and then redissolved in the third process.
[0149] Furthermore, the third step described later can be performed using a dispersion obtained by mixing an oxidant into a reaction solution containing cerium (III) ions, or by adding a stabilizer to a reaction solution after membrane purification of the reaction solution. The concentration of the stabilizer can be arbitrarily set to 0.1–1 M. As a stabilizer, basic amino acids (A), alicyclic amines (B), aromatic heterocyclic compounds containing nitrogen atoms in their ring structure (C), polymers having a heterocyclic amine backbone (D), or boron compounds (E) can be used.
[0150] (3) Third process
[0151] The third step is to perform hydrothermal treatment on the mixture obtained in the second step after adding the oxidant.
[0152] In this invention, hydrothermal treatment is a process of treating with water at a temperature above 100°C and a pressure above 101 kPa (1 atmosphere). Hydrothermal treatment improves the colorability of cerium oxide nanoparticles. When the dispersion containing cerium oxide nanoparticles is colored yellow, orange, red, brown, etc., hydrothermal treatment changes it to a transparent or very light yellow. The effect of hydrothermal treatment depends on the temperature and time of the treatment. Regarding the treatment temperature, the higher the temperature and the longer the reaction time, the more significantly the colorability is improved. The pressure during hydrothermal treatment can be determined using a saturated water vapor pressure gauge and the temperature. Hydrothermal treatment can be carried out at a temperature above 100°C (101 kPa) and below 230°C (2.80 MPa), preferably 105°C (121 kPa) to 200°C (1.55 MPa), more preferably 110°C (143 kPa) to 180°C (1.00 MPa). Furthermore, the time can be arbitrarily set between 1 and 180 minutes. Even with the same heat treatment, if the heating is carried out at a temperature not exceeding 100°C and a pressure exceeding 101 kPa, the colorability will not improve.
[0153] The hydrothermal treatment of this invention involves adding a reaction solution containing an oxidant to a pressure-resistant container and heating it. For example, the reaction solution can be added to a pressure-resistant container consisting of an inner PTFE cylinder and an outer pressure-resistant stainless steel cylinder, and then heated using an oil bath. Alternatively, a purified dispersion can be added to a culture medium bottle and sterilized using a sterilization device such as Tomy Kogyo Co., Ltd.'s LSX-500.
[0154] During hydrothermal treatment, the pH of the reaction solution after adding the oxidant can be below 7, more preferably below 5. Hydrochloric acid, nitric acid, etc., can be used for pH adjustment.
[0155] During hydrothermal treatment, the reaction solution after the addition of an oxidant can be purified using a membrane. Specifically, unreacted cerium(III) ions remaining in the dispersion after the reaction can be removed by filtration using an ultrafiltration membrane or dialysis using a semi-permeable membrane. By removing unreacted cerium(III) ions, the properties of the cerium oxide nanoparticles obtained after hydrothermal treatment are homogenized, and monodisperse nanoparticles can be obtained. Cerium(III) ions can be removed at a concentration of 10 mM or less, preferably 5 mM or less. Furthermore, the nanoparticle concentration can be increased by filtration using an ultrafiltration membrane or dialysis using a semi-permeable membrane. Then, cerium oxide nanoparticles can be separated from the dispersion of the present invention by the methods described later.
[0156] When the particle size of cerium oxide after hydrothermal treatment exceeds 300 nm, the particles can be pulverized to a particle size of 1–300 nm. Examples of pulverization methods include using roller mills, jet mills, hammer mills, pin mills, rotary mills, vibratory mills, planetary mills, ultrafine grinding mills, bead mills, and ultrasonic crushers. Both dry and wet pulverization methods can be used. For wet pulverization, dispersions of hydrothermally treated cerium oxide or dispersions purified as described above can be used. For dry pulverization, cerium oxide dried using methods described later can be used.
[0157] The presence of cerium oxide in the resulting dispersion can be confirmed by obtaining the XANES spectrum described later, which shows a maximum absorption between 5726 eV and 5731 eV, and between 5735 eV and 5739 eV.
[0158] The cerium oxide nanoparticles of the present invention can be separated by drying the dispersion of the present invention using an evaporator, a freeze dryer, or the like. Alternatively, the cerium oxide nanoparticles can be separated by air-drying the dispersion of the present invention by dropping it onto a substrate made of glass, plastic, ceramic, etc., or by drying it in a dryer, or by drying it with a desiccant or a dryer. Furthermore, separation can also be achieved by heating the dispersion of the present invention by dropping it onto a heating block to evaporate the solvent. Additionally, separation can be achieved by drying the dispersion of the present invention using a spray dryer or the like to evaporate the solvent. Furthermore, separation can also be achieved by precipitating the cerium oxide nanoparticles in a centrifuge and removing the supernatant. Furthermore, the cerium oxide nanoparticles can also be separated on a filter membrane by filtering the dispersion of the present invention through ultrafiltration or vacuum filtration to completely remove water. To improve the efficiency of the drying process described above, an azeotropic solvent can be added to the dispersion of the present invention, or the solvent in the dispersion can be replaced with a solvent with a lower boiling point. Furthermore, to improve the efficiency of centrifugation, a co-precipitant, an ionic strength enhancer, or a solvent that reduces the dispersibility of nanoparticles can be added to the dispersion of the present invention. Additionally, prior to the above operations, the size of the nanoparticles in the dispersion of the present invention can be fractionated using ultrafiltration, centrifugation, or the like.
[0159] The dispersion of the present invention may contain ionic components. Examples of ionic components, and components that impart buffering properties, include acetic acid, phthalic acid, succinic acid, carbonic acid, tris(hydroxymethyl)aminomethane (Tris), 2-Morpholinoethanesulfonic acid monohydrate (MES), Bis(2-hydroxyethyl)iminotris(hydroxymethyl)methane (Bis-Tris), N-(2-Acetamido)iminodiacetic acid (ADA), Piperazine-1,4-bis(2-ethanesulfonic acid) (PIPES), and N-(2-Acetamido)-2-aminoethanesulfonic acid. 2-Hydroxy-3-morpholinopropanesulfonic acid (MOPSO), N,N-Bis(2-hydroxyethyl)-2-aminoethanesulfonic acid (BES), 3-Morpholinopropanesulfonic acid (MOPS), N-Tris(hydroxymethyl)methyl-2-aminoethanesulfonic acid (TES), 2-[4-(2-Hydroxyethyl)-1-piperazinyl]ethanesulfonic acid (ACES) 2-Hydroxy-N-tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid (TAPS O), Piperazine-1,4-bis(2-hydroxy-3-propanesulfonic acid) (TAPS O), Piperazine-1,4-bis(2-hydroxy-3-propanesulfonic acid) (Piperazine-1,Examples of components that do not impart buffering properties include 4-bis(2-hydroxy-3-propanesulfonic acid) (POPSO), 2-hydroxy-3-[4-(2-hydroxyethyl)-1-piperazinyl]propanesulfonic acid (HEPSO), 3-[4-(2-hydroxyethyl)-1-piperazinyl]propanesulfonic acid (HEPPS), (Tricine), N,N-Bis(2-hydroxyethyl)glycine (Bicine), and N-Tris(hydroxymethyl)methyl-3-aminopropanesulfonic acid (TAPS). Examples of components that do not impart buffering properties include sodium chloride and potassium chloride. These ionic components can be added at a final concentration ranging from 0.1 mM to 1 M. They can be added to the dispersion after the reaction is complete, or after filtration through an ultrafiltration membrane, or used as a dialysis solvent, or added to the dispersion after dialysis. They can also be added to dried cerium oxide nanoparticles to prepare a dispersion.
[0160] The dispersion of the present invention can be stored as a dispersion after the reaction is completed, or as a purified product obtained by filtering the dispersion after the reaction with an ultrafiltration membrane, or by dialysis with a semi-permeable membrane, or as cerium oxide nanoparticles separated by drying using an evaporator, spray dryer, freeze dryer, etc.
[0161] In the case of producing a dried powder, a dispersant may be added before or after drying to suppress the aggregation of the cerium oxide nanoparticles of the present invention. Preferably, the dispersant is a hydrophilic polymer such as starch, polyvinyl alcohol, polyvinylpyrrolidone, polyacrylic acid, polyethylene oxide, or polyacrylamide; a cationic surfactant such as quaternary ammonium salts; anionic surfactants such as higher fatty acid salts or alkyl sulfate salts; an amphoteric surfactant such as alkyl betaine; a nonionic surfactant such as polyoxyethylene sorbitol fatty acid salt or polyoxyethylene alkyl ether; more preferably, polyvinyl alcohol, polyvinylpyrrolidone, cationic surfactants, or nonionic surfactants.
[0162] Furthermore, the dispersion of the present invention can be stored as a dispersion containing additional solvent components or ionic components such as the aforementioned azeotropic solvent, or as a pH-adjusted dispersant. Refrigeration is preferred when storing the product.
[0163] [Characteristics of cerium oxide nanoparticles]
[0164] When cerium oxide nanoparticles form a dispersion, the particle size can be determined as a hydrodynamic diameter.
[0165] Regarding the hydrodynamic diameter of the cerium oxide nanoparticles of the present invention, the autocorrelation function was derived by measuring dynamic light scattering, and analyzed by the non-negative least squares (NNLS) method. The average particle size was calculated from the number transformation histogram. In the dynamic light scattering measurement, an ELSZ-2000ZS from Otsuka Electronics Co., Ltd. was used. The hydrodynamic diameter of the cerium oxide nanoparticles can be 1–1000 nm, preferably 1–300 nm, more preferably 1–200 nm, further preferably 1–150 nm, and most preferably 1–100 nm.
[0166] The hydrodynamic diameter is determined as a dispersion containing nanoparticles. The determination is performed at 25°C by adjusting the particle concentration to 0.001–1% by mass, the salt concentration to below 100 mM, and the pH to 2–12. For low particle concentrations, membrane concentration and evaporation are performed; for high particle concentrations, solvent dilution is used to adjust the concentration. When the particle concentration of the dispersion is known, the concentration can be adjusted using the above methods. When the cerium oxide concentration is unknown, for example, the cerium ion concentration can be determined by ICP emission spectrometry (ICP-OES) or ICP mass spectrometry (ICP-MS), assuming that all cerium ions are CeO2, and then the concentration is adjusted. If the nanoparticle dispersion does not contain impurities that affect the hydrodynamic diameter value, the hydrodynamic diameter can be directly measured. If the dispersion contains compounds other than cerium oxide nanoparticles that affect the hydrodynamic diameter value, these compounds are removed by membrane purification or similar methods before measurement. If the dispersion contains debris in addition to cerium oxide, the debris is removed by centrifugation, and the supernatant is measured. Alternatively, the dispersion can be subjected to ultrasonic treatment before measurement.
[0167] The cerium oxide nanoparticles of the present invention are characterized in terms of the molar ratio of cerium(III) to cerium(IV) determined by XPS and the energy states of cerium(III) to cerium(IV) determined by XANES spectroscopy.
[0168] In the cerium oxide nanoparticles of this invention, the energy states of cerium(III) and cerium(IV) in Ce₂O₃ and CeO₂ can be observed using X-ray absorption fine structure spectroscopy (XAFS). In XAFS spectra, the structure approximately 20 eV from the absorption end is called XANES (X-ray Absorption Near Edge Structure). Information related to the valence and structure of the target atoms is obtained from XANES. The energy states of cerium(III) and cerium(IV) related to the redox reaction of cerium oxide are reflected in the peak position and peak intensity ratio of the maximum absorption in the XANES spectrum.
[0169] The XANES spectroscopy measurement conditions are as follows: the spectrometer is a Si(111)2 crystal spectrometer, the absorption end is a Ce L3 absorption end, the detection method is transmission, and the detector is an ionization chamber. XANES spectroscopy can be performed on any morphology containing nanoparticles. If the nanoparticles are a dispersion, the particle concentration is adjusted to 1–10% by mass. If the nanoparticles are powders, or composites of powdered nanoparticles with membranes, resins, fibers, etc., the morphology is used for measurement. In the case of thin composite membranes, resins, or fibers, 2–100 layers can be stacked for measurement.
[0170] The cerium oxide nanoparticles of the present invention exhibit maximum absorption in the Ce L3-terminal XANES spectrum obtained by X-ray absorption fine structure spectroscopy in the range greater than 5729 eV and less than 5731 eV, and between 5735 eV and less than 5739 eV. That is, the cerium oxide nanoparticles of the present invention contain the aforementioned basic amino acid, alicyclic amine, aromatic heterocyclic compound, polymer having a heterocyclic amine backbone, or boron compound as a stabilizer, and exhibit maximum absorption in the XANES spectrum in the range greater than 5729 eV and less than 5731 eV, and between 5735 eV and less than 5739 eV.
[0171] In the cerium oxide nanoparticles of this invention, the molar ratio of cerium(III) to cerium(IV) can be determined by X-ray photoelectron spectroscopy (XPS). XPS can obtain information related to elements and valences, and the molar ratio of cerium(III) to cerium(IV) can be quantified using the peak area ratio of the obtained spectra. After calculating the molar ratio of each Ce ion, the obtained spectra are used to make Ce3d... 5 / 2 Ce in 4+ The main peak was corrected for the horizontal axis by setting it to 881.8 eV. Then, the peak splitting of Ce3d was performed to calculate the molar ratio of each Ce ion. The cerium oxide nanoparticles of this invention were all obtained by XPS measurement of Ce content.4+ With Ce 3+ The molar ratio is in the range of 40:60 to 100:0. Cerium oxide nanoparticles can be obtained by XPS determination of Ce... 4+ With Ce 3+ The molar ratio can be 40:60 to 100:0, preferably 50:50 to 100:0, and more preferably 60:40 to 100:0. Ce was determined by XPS. 4+ With Ce 3+ When the molar ratio is specified, a powder obtained by drying the nanoparticles is used. For example, a sample obtained by freeze-drying a dispersion of cerium oxide nanoparticles containing the present invention that has undergone membrane purification is used. Furthermore, if it is a composite of nanoparticles with membranes, resins, or fibers, the surface of the nanoparticles that has been processed is measured.
[0172] That is, the cerium oxide nanoparticles of the present invention contain the above-mentioned basic amino acids, alicyclic amines, aromatic heterocyclic compounds, polymers having a heterocyclic amine skeleton, or boron compounds as stabilizers, and exhibit extremely high absorption in the XANES spectrum in the range greater than 5729 eV and below 5731 eV and between 5735 eV and below 5739 eV, and Ce 4+ With Ce 3+ The cerium oxide nanoparticles of the present invention have a molar ratio of 40:60 to 100:0. Furthermore, in other embodiments, the cerium oxide nanoparticles of the present invention are manufactured by adding an oxidant to a solution containing the aforementioned basic amino acid, alicyclic amine, aromatic heterocyclic compound, polymer having a heterocyclic amine backbone, or boron compound as a stabilizer, and then subjecting it to hydrothermal treatment. In XANES spectroscopy, they exhibit maximum absorption in the range greater than 5729 eV and below 5731 eV and between 5735 eV and below 5739 eV, and Ce... 4+ With Ce 3+ The molar ratio is 40:60 to 100:0.
[0173] As another feature, the cerium oxide nanoparticles involved in this invention are characterized in terms of their crystallinity.
[0174] The Bragg angle (2θ) of the cerium oxide nanoparticles involved in this invention can be determined by X-ray diffraction (XRD). Information related to crystallinity can be obtained from the position and intensity of the peaks in the obtained XRD spectrum.
[0175] The cerium oxide nanoparticles of this invention exhibit diffraction peaks in XRD spectra at Bragg angles 2θ of 27°–29°, 31°–33°, 46°–48°, and 55°–57°. Furthermore, peaks may also be present at 58°–60°, 68°–70°, 75°–77°, 78°–80°, and 87°–90°. A diffraction peak is a maximum intensity value in an XRD spectrum. When determining the Bragg angles exhibiting diffraction peaks, smoothing or other processing can be performed if the intensity of the resulting spectrum is low.
[0176] Furthermore, the cerium oxide nanoparticles of the present invention can achieve a peak intensity ratio of 1.8 or less, preferably 1.7 or less, and more preferably 1.6 or less, in the obtained XRD spectrum of peak intensity at 27°–29° to peak intensity at 46°–48°. In calculating the peak intensity at 27°–29°, the straight line connecting 24° and 36° is first used as the baseline. Next, the Bragg angle of the diffraction peak at 27°–29° is determined. Then, the difference between the intensity of the XRD spectrum at this Bragg angle and the intensity of the baseline is obtained as the peak intensity at 27°–29°. In calculating the peak intensity at 46°–48°, the straight line connecting 44° and 64° is used as the baseline. Next, the Bragg angle of the diffraction peak at 46°–48° is determined. Then, the difference between the intensity of the XRD spectrum at this Bragg angle and the intensity of the baseline is obtained as the peak intensity at 46°–48°.
[0177] That is, the cerium oxide nanoparticles of the present invention are cerium oxide nanoparticles containing the above-mentioned basic amino acids, alicyclic amines, aromatic heterocyclic compounds containing nitrogen atoms in the ring structure, polymers having a heterocyclic amine skeleton, or boron compounds as stabilizers, and having diffraction peaks at Bragg angles (2θ) of 27°–29°, 31°–33°, 46°–48°, and 55°–57° in XRD spectra, with the ratio of the peak intensity at 27°–29° to the peak intensity at 46°–48° being 1.8 or less. In other embodiments, the cerium oxide nanoparticles of the present invention are manufactured by adding an oxidant to a solution containing the aforementioned basic amino acid, alicyclic amine, aromatic heterocyclic compound containing a nitrogen atom in the ring structure, polymer having a heterocyclic amine skeleton, or boron compound and containing cerium(III) ions, and then subjecting it to hydrothermal treatment. In the XRD spectrum, they have diffraction peaks at Bragg angles (2θ°) of 27°–29°, 31°–33°, 46°–48°, and 55°–57°, and the ratio of the peak intensity at 27°–29° to the peak intensity at 46°–48° is 1.8 or less. Particularly preferred are diffraction peaks in XRD spectra at Bragg angles (2θ°) of 27°–29°, 31°–33°, 46°–48°, and 55°–57°, with the ratio of peak intensity at 27°–29° to peak intensity at 46°–48° being 1.8 or less, and the number of diffraction peaks at 5°–80° being 10 or less.
[0178] The zeta potential exhibited by the cerium oxide nanoparticles of the present invention was determined by laser / Doppler electrophoresis. An ELSZ-2000ZS from Otsuka Electronics Co., Ltd. was used for the determination of the zeta potential. The zeta potential is one of the values representing the electrical properties of the interface of a colloid in solution, and it varies depending on pH. In the present invention, the value in a solution with pH 7 was used. The zeta potential exhibited by the cerium oxide nanoparticles can be +10 mV or higher, preferably +15 mV or higher, more preferably +20 mV or higher, and most preferably +25 mV or higher.
[0179] When measuring the Zeta potential of the nanoparticles of the present invention by laser / Doppler method, for example, the dispersion is concentrated by membrane concentration to a particle concentration of 0.001% by mass or more and 1% by mass or diluted with water. The salt strength is then adjusted to 1 to 50 mM, and the pH of the dispersion is adjusted to 7 using nitric acid and sodium hydroxide, and the measurement is performed at room temperature.
[0180] [Applications of cerium oxide nanoparticles]
[0181] The cerium oxide nanoparticles or dispersions thereof of the present invention can be used as antiviral agents. As a method for evaluating the performance as an antiviral agent, the viral load is quantified after the cerium oxide nanoparticles or dispersions thereof of the present invention have been contacted or mixed with a virus. Examples of methods for quantifying the virus include methods for determining viral antigen load by ELISA, methods for quantifying viral nucleic acid by PCR, methods for determining infection titer by plaque assay, and methods for determining infection titer by 50% infection dose assay. In the present invention, the antiviral activity is preferably determined by methods for determining infection titer by plaque assay or 50% infection dose assay. The unit of viral infection titer in the 50% infection dose assay, in the case of testing with cultured cells, is TCID. 50 The median infectious dose (CID) is expressed as 50% of the total infectious dose (TcC) in the case of using incubated eggs. 50 (Egg-infectious dose 50) is expressed as the LD50 in animals. 50 (Median lethal dose, 50). Furthermore, methods for calculating the infection titer from data obtained in the 50% infection dose assay include the Reed-Muench method, the Behrens-Kaeber method, and the Spearman-Karber method, but the Reed-Muench method is preferred in this invention. The criteria for determining antiviral activity are generally as follows: if the logarithmic decrease in infection titer relative to the infection titer before the application of the cerium oxide nanoparticles of this invention, compared to a control without the nanoparticles of this invention, is 2.0 or higher, then the antiviral activity is considered effective.
[0182] Furthermore, a suitable embodiment of the dispersion of cerium oxide nanoparticles comprising the present invention is a dispersion comprising a boron compound and cerium oxide nanoparticles, wherein the viral infection titer TCID in a 50% infection dose determination method for virus inactivation assays targeting cell culture is used. 50 The logarithmic decrease value, relative to the infection titer before the application of the cerium oxide nanoparticles of the present invention, is 2.0 or higher than that of the control without the nanoparticles of the present invention. The viral infection titer TCID in the virus inactivation test... 50 The logarithmic reduction value is 2.0 or higher, thus allowing it to be used as an antiviral agent. The logarithmic reduction value of the viral infection titer is preferably 2.5 or higher, particularly preferably 3.0 or higher.
[0183] Examples of viruses that can be inactivated by the cerium oxide nanoparticles or dispersions thereof of the present invention include, for example, rhinovirus, poliovirus, foot-and-mouth disease virus, rotavirus, norovirus, enterovirus, hepatitis virus, astrovirus, sap virus, hepatitis E virus, influenza A, B, and C viruses, parainfluenza virus, mumps virus, measles virus, human metapneumovirus, RS virus, Nipah virus, Hendra virus, yellow fever virus, dengue virus, Japanese encephalitis virus, West Nile virus, hepatitis B and C viruses, eastern and western equine encephalitis virus, Angioniang virus, and wind. Herpesviruses, Lassa virus, Junin virus, Machupo virus, Guanareto virus, Sabya virus, Crimean-Congo hemorrhagic fever virus, sandfly fever, Hantavirus, Sinup virus, rabies virus, Ebola virus, Marburg virus, bat lyssa virus, human T-cell leukemia virus, human immunodeficiency virus, human coronavirus, SARS coronavirus, SARS coronavirus 2, human parvovirus, polyomavirus, human papillomavirus, adenovirus, herpesvirus, varicella-zoster virus, Epstein-Barr virus, cytomegalovirus, smallpox virus, monkeypox virus, vaccinia virus, molluscum contagiosum virus, parapoxvirus, etc.
[0184] When used as an antiviral agent, the cerium oxide nanoparticles or dispersions of the present invention can be incorporated as additives into materials such as fibers, tubes, beads, rubber, membranes, and plastics, or coated onto the surface of these materials. For example, they can be used in various areas as plastic parts such as masks, medical caps, medical shoe covers, air conditioner filters, air purifier filters, vacuum cleaner filters, exhaust fan filters, vehicle filters, air conditioning filters, air conditioner fans, and air conditioner vent louvers, as well as blowers, automotive air conditioner fans, automotive air conditioner vent louvers, as well as blowers, clothing, bedding, screen nets, chicken coop nets, mosquito nets, wallpaper, windows, curtains, interior materials for buildings such as hospitals, interior materials for trams and automobiles, vehicle seats, curtains, chairs, sofas, virus treatment equipment, doors, ceilings, floors, and windows.
[0185] The cerium oxide nanoparticles or their dispersions of the present invention can be used as antibacterial agents.
[0186] As a method for evaluating the performance of an antimicrobial agent, EN1040:2005, a European Norm (EN) standard test method, can be cited as an example. In this test method, a bacterial suspension is added to a test solution containing the active ingredient of the antimicrobial agent, and the bacterial count is determined after a certain period of time. The bacterial suspension contains 0.85% NaCl and 0.1% tryptone as culture medium components, and is mixed in a volume ratio of test solution to bacterial suspension of 9:1. The criterion for determining antimicrobial activity is generally that if the logarithmic decrease in the bacterial count relative to the bacterial count before the application of the cerium oxide nanoparticles of the present invention, compared to a control without the nanoparticles of the present invention, is 2.0 or more, then antimicrobial activity is determined. As a method for quantifying the bacterial count, methods for determining the bacterial count by turbidity (OD600) measurement, methods for determining the bacterial count by colony formation method, and methods for quantifying the nucleic acid of the bacteria by PCR can be cited. In the present invention, the antimicrobial activity is preferably determined by methods for determining the infection titer by turbidity measurement and colony formation method.
[0187] Furthermore, a suitable embodiment of the dispersion containing the cerium oxide nanoparticles of the present invention is one that contains a boron compound and cerium oxide nanoparticles, wherein the logarithmic reduction in bacterial count relative to the infection titer before the application of the cerium oxide nanoparticles of the present invention, compared to a control without the nanoparticles of the present invention, is 2.0 or more. The presence of a logarithmic reduction in bacterial count of 2.0 or more in an antibacterial test allows it to be used as an antibacterial agent. The logarithmic reduction in bacterial count is preferably 2.5 or more, and particularly preferably 3.0 or more.
[0188] Microorganisms that exhibit antibacterial activity as the cerium oxide nanoparticles or dispersions thereof of the present invention can be categorized as follows: As bacteria, Gram-positive bacteria and Gram-negative bacteria can be included. Examples of Gram-negative bacteria include, for example, bacteria of the genus *Escherichia coli* such as *Escherichia coli*, bacteria of the genus *Salmonella* such as *Salmonella*, bacteria of the genus *Pseudomonas* such as *Pseudomonas aeruginosa*, bacteria of the genus *Shigella* such as *Shigella*, bacteria of the genus *Klebsiella pneumoniae* such as *Klebsiella pneumoniae*, and bacteria of the genus *Legionella* such as *Legionella pneumophila*. Examples of Gram-positive bacteria include, for example, bacteria of the genus *Staphylococcus* such as *Staphylococcus*, bacteria of the genus *Bacillus* such as *Bacillus subtilis*, and bacteria of the genus *Mycobacterium* such as *Mycobacterium tuberculosis*. Examples of fungi include fungi and yeasts. Examples of fungi include filamentous fungi of the genus *Aspergillus* such as *Aspergillus niger*, filamentous fungi of the genus *Penicillium* such as *Penicillium*, filamentous fungi of the genus *Cladosporium* such as *Cladosporium*, filamentous fungi of the genus *Alternaria* such as *Alternaria*, filamentous fungi of the genus *Trichoderma* such as *Trichoderma*, and filamentous fungi of the genus *Chaetomium* such as *Chaetomium*. Examples of yeasts include yeasts of the genus *Saccharomyces* such as baker's yeast and brewer's yeast, and yeasts of the genus *Candida* such as *Candida albicans*.
[0189] The cerium oxide nanoparticles of the present invention can be used for antibacterial processing by adding them during the molding of fibers, tubes, beads, rubber, membranes, plastics, etc., or by coating them as a dispersion onto their surfaces. Examples of articles that can be antibacterial processed using the cerium oxide nanoparticles or dispersions of the present invention include, for example, radially perforated drain covers for kitchen sinks, drain plugs, window glass fixing gaskets, mirror fixing gaskets, waterproof gaskets for bathrooms, washbasins, or kitchens, refrigerator door gaskets, bath mats, anti-slip rubber for washbasins or chairs, hoses, shower heads, gaskets for water purifiers, plastic products for water purifiers, gaskets for washing machines, plastic products for washing machines, masks, medical caps, medical shoe covers, air conditioner filters, and air purifier filters. Plastic components such as filters for vacuum cleaners, exhaust fans, vehicles, and air conditioners, as well as blowers, are used in various applications including air conditioners, vacuum cleaner filters, exhaust fan filters, vehicle filters, air conditioner fans, air conditioner vent louvers, etc.; clothing, bedding, screens, chicken coop nets, mosquito nets, wallpaper, windows, curtains, interior materials for buildings such as hospitals, interior materials for trams and automobiles, vehicle seats, curtains, chairs, sofas, virus treatment equipment, doors, ceilings, floors, windows, and other building materials. Thus, products processed using the dispersion of cerium oxide nanoparticles of this invention can be used as sanitary materials in various areas.
[0190] By adding the cerium oxide nanoparticles or their dispersions of the present invention to a disinfectant, antiviral or antibacterial effects can be imparted to the disinfectant. As a disinfectant, it can be applied to disinfectants containing disinfectant components such as chlorine-based, iodine-based, peroxide-based, aldehyde-based, phenolic-based, biguanide-based, mercury-based, alcohol-based, anionic surfactants, cationic surfactants, amphoteric surfactants, nonionic surfactants, and naturally derived surfactants as active ingredients. Furthermore, by adding the cerium oxide nanoparticles or their dispersions of the present invention to a liquid containing ultrafine bubbles, antiviral or antibacterial effects can be imparted.
[0191] In the case of liquid disinfectant, the concentration of cerium oxide nanoparticles of the present invention can be arbitrarily set between 0.0001% by mass and 10% by mass.
[0192] Examples of chlorine-based disinfectants include sodium hypochlorite, chlorine gas, and isocyanuric acid chloride.
[0193] Examples of iodine-based disinfectants include iodine, povidone-iodine, nonyl alcohol ether iodine, and phenoxy iodine.
[0194] Examples of peroxide-based disinfectants include hydrogen peroxide, potassium permanganate, peracetic acid, organic peracids, sodium percarbonate, sodium perborate, and ozone.
[0195] Examples of aldehyde-based disinfectants include glutaraldehyde, benzodialdehyde, and formaldehyde.
[0196] Examples of phenolic disinfectant components include isopropyl methylphenol, thymol, eugenol, triclosan, cresol, phenol, chlorocresol, p-chloro-m-cresol, p-chloro-m-xylenol, o-phenylphenol, alkyl p-hydroxybenzoate, resorcinol, hexachlorophenol, salicylic acid or its salts, etc.
[0197] Examples of biguanide-based disinfectant ingredients include chlorhexidine, chlorhexidine gluconate, and chlorhexidine hydrochloride.
[0198] Examples of mercury-based disinfectants include merbromin, mercuric chloride, and thimerosal.
[0199] Examples of alcohol-based disinfectants include ethanol and isopropanol. In this case, the concentration of the alcohol-based disinfectant can be 30–80% by mass.
[0200] Examples of disinfectant components that are anionic surfactants include alkylbenzene sulfonates, fatty acid salts, higher alcohol sulfates, polyoxyethylene alkyl ether sulfates, α-sulfonyl fatty acid esters, α-olefin sulfonates, monoalkyl phosphates, and alkyl sulfonates.
[0201] Examples of cationic surfactant disinfectant components include alkyl trimethylammonium salts, dialkyl dimethylammonium salts, alkyl dimethyl benzylammonium salts, polyhexamethylene biguanide, and benzyl chloride.
[0202] Examples of disinfectant components that are amphoteric surfactants include alkyl amino fatty acid salts, alkyl betaines, and alkyl amine oxides.
[0203] Examples of nonionic surfactant disinfectant components include polyoxyethylene alkyl ethers, polyoxyethylene / polyoxypropylene alkyl ethers, polyoxyethylene / polyoxybutene alkyl ethers, alkylamine ethoxylates, alkylamine alkoxylates, polyoxyethylene-polyoxypropylene block copolymers, polyoxyethylene-polyoxypropylene block copolymers (reverse type), ethylene oxide / propylene oxide adducts of polyols, alkyl glucosides, and fatty acid alkanolamides.
[0204] Examples of disinfectant components derived from natural sources include plant-based agents such as pine phenol, anethole, fennel oil, borneol, camphor, carvone, cinnamon oil, quinoa oil, eucalyptol, citral, citronellol, eugenol, pinene, geraniol, lemon oil, linalool, menthol, orange oil, safrole, thymol, and polyphenols (flavanols, gallic tannins, ellagic tannins, and brown algal polyphenols); chitosans and deacetylated chitosans made from crustacean shells; animal-based agents such as calcined shell powder obtained by calcining scallop and oyster shells; microbial agents such as polylysine; and enzyme-based agents such as lysozyme. In addition, antimicrobial peptides produced by organisms to defend themselves from external microbial influences can also be used, such as histamine, defensin, lactoferrin, lactoferricin peptide (a breakdown product of lactoferrin), magainin, cecropin, and melititin.
[0205] In addition, plant extracts can be used as disinfectant ingredients derived from natural sources. Specific examples include grapefruit seed extract, Kochia scoparia (from the Chenopodiaceae family), Belamcanda chinensis (from the Iridaceae family), St. John's wort (from the Clusiaceae family), Boswellia carterii and Populus tomentosa (from the Burseraceae family), Adenophora stricta (from the Campanulaceae family), Echinacea purpurea, Matricaria champaca, Arctium lappa, Solidago virgaurea, and Atractylodes lancea (from the Asteraceae family), Coptis chinensis (from the Ranunculaceae family), Lonicera japonica (from the Caprifoliaceae family), Lauraceae (from the Lauraceae family), Hops (from the Moraceae family), Scutellaria baicalensis, Oregano, Nepeta cataria, Salvia miltiorrhiza, Thyme, Lemon balm, Ramulus japonica, Lavender, and Rosemary (from the Lamiaceae family), Zingiber officinale and Zingiber officinale (from the Zingiberaceae family), Elderberry (from the Caprifoliaceae family), Japanese cedar (from the Taxaceae family), Angelica dahurica and Saposhnikovia divaricata (from the Apiaceae family), and Polygonaceae. Plant extracts from various plants including: * Polygonum aviculare*, *Ardisia crenata* (Ericaceae), *Houttuynia cordata* (Saururaceae), *Tribulus terrestris* (Zaruziaceae), *Vitaceae*, *Allium chinense* (Myrtaceae), *Tea tree*, *Eucalyptus*, *Syringa vulgaris* (Fabaceae), *Sophora japonica* (Fabaceae), *Dalbergia cochinchinensis*, *Millettia speciosa* (Fabaceae), *Liquidambar formosana* (Hamamellaceae), *Phellodendron chinense* (Rutaceae), *Citrus reticulata*, *Comfrey* (Borneolaceae), *Berberis vulgaris* (Berberis thunbergii), *Nandina domestica* (Berberis thunbergii), *Magnolia officinalis* (Magnoliaceae), *Sanguisorba officinalis* (Rosaceae), *Mallotus arvense* (Loranthus parasiticus) (Moraceae), *Anemarrhena asphodeloides* (Liliaceae), *Aspidistra elatior* (Ligusticum striatum), *Glycyrrhiza uralensis* (Liliaceae), *Gentiana macrophylla* (Gentianaceae), *Phyllostachys pubescens* (Poaceae), and *Brown algae* (Fucus veitchii).
[0206] Ultrafine bubbles can be categorized as bubbles with a particle size of less than 500 nm that contain one or more gases selected from air, oxygen, hydrogen, nitrogen, carbon dioxide, argon, neon, xenon, fluorinated gases, ozone, and inert gases. Ultrafine bubbles are also known as nanobubbles. Concentrations can reach 100,000 bubbles / ml or higher.
[0207] In addition to the disinfecting components described above, disinfectants containing cerium oxide nanoparticles or dispersions of the present invention may also contain any appropriate components depending on their dosage form. Specifically, they may contain solvents, wetting agents, thickeners, antioxidants, pH adjusters, amino acids, preservatives, sweeteners, flavorings, surfactants, colorants, adjuvants that enhance bactericidal effects, chelating agents, ultraviolet absorbers, defoamers, enzymes, formulation stabilizers, etc.
[0208] Disinfectants containing cerium oxide nanoparticles or dispersions thereof of the present invention can be provided in various forms, such as liquid, gel, and powder. Liquid disinfectants can be provided as detergents, sprays, etc., and can be filled into bottles with metering caps, trigger-type spray containers, squeeze-type or dispenser-type pump spray containers, etc., for dispersing or spraying. Liquid disinfectants can be impregnated in sheets of paper, cloth, etc., and filled into containers such as bottles or barrels, and provided as wet sheets.
[0209] By adding the cerium oxide nanoparticles or their dispersion of the present invention to a coating, the coating can be endowed with antiviral properties. In this case, for the purpose of immobilizing the cerium oxide nanoparticles of the present invention in a coating film, a resin emulsion composition may be included in the coating.
[0210] Examples of resin emulsion compositions include, for instance, ethylene vinyl acetate resin emulsions, vinyl chloride resin emulsions, epoxy resin emulsions, acrylic resin emulsions, urethane resin emulsions, acrylic silicone resin emulsions, fluororesin emulsions, or synthetic resin emulsions composed of resin components such as composites thereof. The mass ratio of the cerium oxide nanoparticles of the present invention added to the coating to the solid components in the resin emulsion can be arbitrarily set between 0.01:99.99 and 99.99:0.01.
[0211] The ethylene-vinyl acetate copolymer resin emulsion is obtained by copolymerizing ethylene and vinyl acetate monomers. It can also be further copolymerized with vinyl monomers having functional groups such as primary amino, secondary amino, tertiary amino, quaternary amino, carboxyl, epoxy, sulfonic acid, hydroxy, hydroxymethyl, and alkoxy acid groups.
[0212] Vinyl chloride copolymer resin emulsion is obtained by polymerizing vinyl chloride, and can be further copolymerized with vinyl monomers having functional groups such as primary amino, secondary amino, tertiary amino, quaternary amino, carboxyl, epoxy, sulfonic acid, hydroxy, hydroxymethyl, and alkoxy acid groups.
[0213] Monomers that can be used in the preparation of acrylic resin emulsions include methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, octadecyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, nonyl methacrylate, dodecyl methacrylate, stearyl methacrylate, isobornyl methacrylate, dicyclopentyl methacrylate, phenyl methacrylate, benzyl methacrylate, etc. (meth)acrylate monomers; acrylic acid, methacrylic acid, β-carboxyethyl (meth)acrylate, 2-(meth)acryloylpropionic acid, crotonic acid, etc. Monomers containing carboxyl groups and unsaturated bonds, such as itaconic acid, maleic acid, fumaric acid, itaconic acid half ester, maleic acid half ester, maleic anhydride, and itaconic anhydride; polymerizable monomers containing glycidyl acrylate and allyl glycidyl ether, such as glycidyl acrylate; polymerizable monomers containing hydroxyl groups, such as 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, polyethylene glycol mono(meth)acrylate, and mono(meth)acrylate glyceryl acrylate; ethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, diallyl phthalate, divinylbenzene, and allyl acrylate, etc.
[0214] Examples of monomers that can be used in the preparation of urethane resin emulsions, and examples of polyisocyanates, include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-biphenyl diisocyanate, 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3'-dichloro-4,4'-biphenyl diisocyanate, 1,5-naphthalene diisocyanate, 1,5-tetrahydronaphthalene diisocyanate, tetramethylene diisocyanate, and 1,6-hexamethylenediisocyanate. Examples of diol components include esters, 1,12-dodecane diisocyanate, trimethylhexamethylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, phenylenediamine diisocyanate, tetramethylphenylenediamine diisocyanate, hydrogenated phenylenediamine diisocyanate, lysine diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, and 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate. Examples of polyol components include polyester polyols, polyether polyols, polycarbonate polyols, polyacetal polyols, polyacrylate polyols, polyesteramide polyols, polysulfide polyols, and polyolefin polyols such as polybutadiene-based polyols.
[0215] Examples of silicon-containing acrylic monomers that can be used in the preparation of acrylic silicone resin emulsions include γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, γ-(meth)acryloyloxypropylmethyldimethoxysilane, and γ-(meth)acryloyloxypropylmethyldiethoxysilane.
[0216] Monomers that can be used in the preparation of fluoropolymer emulsions include fluoroolefins (1,1-difluoroethylene, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, pentafluoroethylene, hexafluoropropylene, etc.) and fluorinated (meth)acrylates ((meth)acrylate trifluoroethyl ester, (meth)acrylate pentafluoropropyl ester, (meth)acrylate perfluorocyclohexyl ester, etc.).
[0217] Coatings containing cerium oxide nanoparticles or dispersions thereof of the present invention may, as needed, contain pigments, matting materials, aggregates, fibers, crosslinking agents, plasticizers, preservatives, mildew inhibitors, antibacterial agents, defoamers, viscosity modifiers, leveling agents, pigment dispersants, antisettling agents, anti-sagging agents, ultraviolet absorbers, light stabilizers, antioxidants, adsorbents, etc. These components may be formulated individually or in combination into the coating composition.
[0218] Coatings containing cerium oxide nanoparticles or dispersions thereof, incorporating the present invention, can be used, for example, for coating interior surfaces of buildings. Examples of interior surfaces include, for instance, mortar, concrete, gypsum board, wall panels, extruded boards, slate boards, asbestos cement boards, fiber-infused cement boards, calcium silicate boards, ALC boards, metals, wood, glass, rubber, ceramics, fired tiles, porcelain tiles, plastics, synthetic resins, and other substrates, fabrics, wallpaper, or coatings formed on these substrates. Furthermore, they can also be applied to exterior surfaces of buildings and structures other than buildings.
[0219] A resin composition containing cerium oxide nanoparticles of the present invention can be prepared by adding a dispersion of cerium oxide nanoparticles or nanoparticles containing the present invention to a base resin (base resin). Such a resin composition can be prepared with excellent color and exhibiting oxidative decomposition properties against harmful substances such as viruses and bacteria.
[0220] The type of base resin is not limited; it can be any of thermoplastic resins or thermosetting resins, and can be a homopolymer, a copolymer, or a blend of two or more polymers. From the viewpoint of good moldability, thermoplastic resins are preferred.
[0221] As thermoplastic resins, the following can be used: polyethylene, polypropylene, polystyrene, polymethylpentene and other polyolefins, alicyclic polyolefins, acrylonitrile-styrene resin (AS resin), acrylonitrile-butadiene-styrene resin (ABS resin) and other styrene-based resins, nylon 6, nylon 66 and other polyamides, polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, polybutylene succinate and other polyesters, polycarbonate, polyarylates, polyacetals, polyphenylene sulfide, vinyl chloride, tetrafluoroethylene, trifluoroethylene, trifluorochloroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, 1,1-difluoroethylene and other fluorinated resins, aromatic polyamides, polyimides, acrylic resins, methacrylic resins, polyacetals, polyglycolic acid, polylactic acid, etc. Examples of thermosetting resins include phenolic resins, epoxy resins, urea resins, melamine resins, unsaturated polyesters, polyurethanes, polyimides, silicone resins, etc.
[0222] The resin composition of the present invention is obtained by adding the cerium oxide nanoparticles of the present invention to a base resin. The method of adding the cerium oxide nanoparticles is not particularly limited. For example, they can be added to a base resin that has been molten by heat or the like and then compounded; they can also be melt-compounded after being mixed with the base resin at a predetermined ratio; or they can be added to the base resin together with additives such as flame retardants, plasticizers, antistatic agents, antioxidants, lightfastness agents, hydrolysis inhibitors, pigments, and lubricants. Furthermore, by exposing the cerium oxide nanoparticles of the present invention to the resin surface, they are biased, thereby increasing the contact efficiency with harmful substances such as viruses and bacteria, thus achieving a sufficient effect. The biasing method is not particularly limited, but when additives are used in conjunction, the biasing efficiency can be improved by selecting additives with a relatively high affinity for the cerium oxide nanoparticles of the present invention compared to the base resin. Examples of such additives include higher fatty acids, acid esters, acid amides, higher alcohols, and low- or high-molecular-weight polymers of surfactants; however, there are no particular limitations as long as they have an affinity for the cerium oxide nanoparticles of the present invention, and they can be preferably used. In addition, they can be combined into one or more types.
[0223] The cerium oxide nanoparticles of the present invention, added to the base resin, can be in any form, including powder, granules, slurry, aqueous dispersion, or organic solvent dispersion, and can be melt-blended using known methods without particular limitation. Furthermore, the cerium oxide nanoparticles of the present invention can be added to the base resin together with a dispersant, or as a mixture with a dispersant. The dispersant for the cerium oxide nanoparticles of the present invention is not particularly limited, but surfactants are preferred. Cationic surfactants such as quaternary ammonium salts, anionic surfactants such as higher fatty acid salts or alkyl sulfate salts, amphoteric surfactants such as alkyl betaine, polyoxyethylene sorbitol fatty acid salts, and nonionic surfactants such as polyoxyethylene alkyl ethers can all be used, but cationic and nonionic surfactants are more preferred. The mixing ratio of the dispersant to the cerium oxide nanoparticles of the present invention is not particularly limited and can be adjusted arbitrarily as long as it does not significantly impair the compatibility and oxidative activity with the added base resin.
[0224] Regarding the content of cerium oxide nanoparticles relative to the overall resin composition of the present invention, there is no particular limitation as long as it can decompose harmful substances such as viruses and bacteria, but it is preferably 0.01% by mass or more and 60% by mass or less. If the content is less than 0.01% by mass, it cannot exert a sufficient effect; furthermore, if it is more than 60% by mass, it may sometimes impair the mechanical properties of the resin, such as strength and durability. Preferably, it is 0.05% by mass or more and 50% by mass or less. More preferably, it is 0.1% by mass or more and 30% by mass or less. Further preferably, it is 3% by mass or more and 10% by mass or less. In addition, the resin composition of the present invention can be used as a masterbatch and mixed with a resin that is the same as or different from the base resin at a predetermined ratio. When preparing a masterbatch, the content of cerium oxide nanoparticles of the present invention is preferably 10% by mass or more.
[0225] The method for manufacturing the resin composition of the present invention is not particularly limited, and methods such as mixing the components constituting the resin composition using a mixer or uniformly melting and mixing them are examples. Examples of mixers include, for instance, V-type stirrers, high-speed mixers, suspension high-speed mixers, and Henschel mixers. The melt mixing temperature is preferably 200°C to 320°C, more preferably 200°C to 300°C. The resulting resin composition can be granulated using a granulator for use.
[0226] The resin composition of the present invention can be molded by any molding method. Examples of molding methods include injection molding, extrusion molding, blow molding, blow molding, vacuum molding, compression molding, and gas-assisted molding.
[0227] The resin composition of the present invention is characterized by its superior color tone compared to resins containing conventional cerium oxide nanoparticles. The yellowness index of the resin composition of the present invention is preferably 15 or less, more preferably 10 or less, and even more preferably 5 or less. Here, yellowness index refers to a value measured using a color computer (manufactured by Suga Test Machine Co., Ltd.) according to JIS-K7373.
[0228] The resin composition of the present invention can be widely used as molded articles of any shape. Examples of molded articles include injection molded articles, extruded articles, vacuum-molded articles, blow-molded articles, sheets, fibers, cloths, non-woven fabrics, and composites with other materials.
[0229] Using the resin composition of the present invention as a raw material, resin products such as automotive interior materials, electrical product housings, hanging handles, armrests, door handles, and partitions can be manufactured.
[0230] Resin compositions containing cerium oxide nanoparticles of the present invention and their molded articles can be used as antiviral resins. As a method for evaluating the performance as an antiviral resin, the viral load is quantified after the molded article of the resin composition of the present invention has been contacted with a virus. Examples of methods for quantifying the virus include methods for determining viral antigen load by ELISA, methods for determining viral nucleic acid load by PCR, methods for determining infection titer by plaque assay, and methods for determining infection titer by 50% infection dose assay. In the present invention, the antiviral performance is preferably achieved by methods for determining infection titer by plaque assay or 50% infection dose assay. The unit of viral infection titer in the 50% infection dose assay, when cultured cells are used as the test subject, is TCID. 50 The median infectious dose (50%) is expressed as the result of EID when incubated eggs are used. 50 (Egg infectious dose 50) is expressed as the percentage of infectious doses in animals determined by the LD50. 50 (Median lethal dose, 50). Furthermore, methods for calculating infection titers from data obtained in the 50% infection dose assay include the Reed-Muench method, the Behrens-Kaeber method, and the Spearman-Karber method, but the Reed-Muench method is used in this invention. The criteria for determining antiviral performance are generally as follows: if the logarithmic reduction in infection titer relative to the infection titer before application of the resin composition of this invention, compared to a control containing cerium oxide nanoparticles of this invention, is 2.0 or more, then the antiviral performance is deemed effective.
[0231] Fiber materials containing cerium oxide nanoparticles of the present invention can be obtained by immobilizing the cerium oxide nanoparticles of the present invention on a fiber substrate, or by spinning a resin composition incorporating the cerium oxide nanoparticles of the present invention. The method of immobilizing the cerium oxide nanoparticles of the present invention on a fiber substrate is preferred because the cerium oxide nanoparticles are exposed on the surface of the resulting fiber material, making it easier to exhibit antiviral and antibacterial properties.
[0232] As a method for immobilizing the cerium oxide nanoparticles of the present invention onto a fiber substrate, a suitable method is to immobilize a dispersion containing the cerium oxide nanoparticles of the present invention onto the fiber substrate using an online or offline coating apparatus, by means of impregnation, spraying, coating, or the like. Here, examples of coating apparatus include a roll-up mill, a sprayer, a sizing press coater, a light-touch roller coater, a doctor blade coater, a bar coater, an air knife coater, a light-touch die coater, a slit coater, and a gravure coater.
[0233] When the cerium oxide nanoparticles of the present invention are immobilized on the above-mentioned fiber substrate, it is preferable to add an adhesive component that serves as a binder to the fiber substrate to the dispersion, which can suppress the detachment of the cerium oxide nanoparticles from the fiber substrate.
[0234] Examples of adhesive components include acrylic resins, epoxy resins, melamine resins, urethane resins, polyamide resins, polyimide resins, polyester resins, urea resins, phenolic resins, silicone resins, vinyl chloride resins, fluoropolymers, and non-fluorinated water-repellent resins, but are not limited to these, and are preferably used. Here, examples of non-fluorinated water-repellent resins include hydrocarbon-based urethane resins and hydrocarbon-based acrylic resins.
[0235] In particular, when using a fiber substrate containing cerium oxide nanoparticles of the present invention as the fabric for protective clothing, the adhesive component is preferably a polyamide resin or a non-fluorinated water-repellent resin. When a polyamide resin is used as the adhesive component, the antistatic properties of the fiber substrate containing the cerium oxide nanoparticles of the present invention become good. Furthermore, when a hydrocarbon-based water-repellent resin is used, the decrease in water pressure resistance of the fiber substrate containing the cerium oxide nanoparticles of the present invention caused by resin processing of the fiber substrate can be suppressed.
[0236] Furthermore, the ionicity of the binder component is preferably cationic or nonionic, and more preferably cationic. By using a cationic or nonionic binder component, the stability of the dispersion becomes good when mixed with the cerium oxide nanoparticles of the present invention.
[0237] Furthermore, particularly when using a fiber substrate containing cerium oxide nanoparticles of the present invention as the fabric for protective clothing, the mass mixing ratio of the adhesive component to the cerium oxide nanoparticles of the present invention (adhesive component / cerium oxide nanoparticles) is preferably 0.35 or more and 1.45 or less. By having the mixing ratio of the adhesive component to the cerium oxide nanoparticles of the present invention (adhesive component / cerium oxide nanoparticles) be 0.35 or more, the shedding of the cerium oxide nanoparticles of the present invention from the fiber substrate can be suppressed. On the other hand, by having the mixing ratio of the adhesive component to the cerium oxide nanoparticles of the present invention (adhesive component / cerium oxide nanoparticles) be 1.45 or less, the cerium oxide nanoparticles are exposed on the surface of the resulting fiber material, making it easier to exert antiviral and antibacterial properties.
[0238] When the adhesive component is added to immobilize the cerium oxide nanoparticles of the present invention onto the aforementioned fiber substrate, it is preferable to also add a crosslinking agent, thereby preventing the detachment of the cerium oxide nanoparticles of the present invention from the protective clothing using the fiber substrate containing the cerium oxide nanoparticles of the present invention. By preventing the detachment of the cerium oxide nanoparticles of the present invention from the protective clothing, the antiviral performance of the protective clothing becomes excellent. Examples of such crosslinking agents include melamine resin, etc. Azoline resins, urea resins, phenolic resins, epoxy resins, blocked isocyanates, etc., but not limited to these, may be preferred applications.
[0239] Furthermore, when immobilizing the cerium oxide nanoparticles of the present invention onto the aforementioned fiber substrate, additives for controlling the dispersibility and viscosity of the cerium oxide nanoparticles of the present invention can be added to the dispersion.
[0240] As an additive, surfactants are preferred. Cationic surfactants such as quaternary ammonium salts, anionic surfactants such as higher fatty acid salts and alkyl sulfate salts, amphoteric surfactants such as alkyl betaine, nonionic surfactants such as polyoxyethylene sorbitol fatty acid salts and polyoxyethylene alkyl ethers can all be used, but cationic surfactants and nonionic surfactants are more preferred.
[0241] Regarding the mixing ratio of the additive to the cerium oxide nanoparticles of the present invention, there are no particular limitations as long as the antiviral and antibacterial properties are not significantly impaired, and it can be adjusted arbitrarily. On the other hand, in cases where the fiber substrate containing the cerium oxide nanoparticles of the present invention is required to withstand water pressure, such as in the fabric used in protective clothing, considering factors that reduce water pressure resistance, the mixing ratio of the surfactant to the cerium oxide nanoparticles of the present invention (surfactant / cerium oxide nanoparticles) is preferably 0.02 or less, more preferably 0.01 or less, and even more preferably 0.002 or less. It is particularly more preferable not to add surfactants or the like.
[0242] When spinning using the resin composition of the present invention, a thermoplastic resin is preferably used as the base resin. As a spinning method, for example, the resin composition of the present invention is formed into a molten polymer and introduced to a spinning assembly via piping. The polymer introduced from the polymer inlet of the spinning assembly passes through a filter layer composed of filter media / filters and is discharged from the outlet orifice of the spinneret to obtain fibers.
[0243] The type of fiber substrate is not limited and can be any of natural fibers, synthetic fibers, and inorganic fibers, or a mixture or composite fiber of two or more of them. Examples of natural fibers include, but are not limited to, cellulose-based fibers such as cotton, linen, and rayon, and animal fibers such as wool, silk, and down; these are preferred applications. Examples of synthetic fibers include, but are not limited to, polyolefin-based fibers, polyester-based fibers, polyamide-based fibers, acrylic-based fibers, polyurethane-based fibers, and polyvinyl alcohol-based fibers; these are preferred applications. Examples of inorganic fibers include, but are not limited to, glass fibers, carbon fibers, and ceramic fibers; these are preferred applications. Furthermore, fibers that have undergone processing such as irregular cross-sections or hollow structures are also preferred applications. Examples of fiber forms include filaments, woven fabrics, and nonwoven fabrics; these are preferred applications.
[0244] Among these, especially when using a fiber substrate containing cerium oxide nanoparticles of the present invention as the fabric for protective clothing, from the viewpoint of excellent productivity and strength, the aforementioned fiber substrate is preferably in the form of a nonwoven fabric. Specific examples of nonwoven fabrics include resin-bonded dry nonwoven fabrics, thermally bonded dry nonwoven fabrics, spunbond dry nonwoven fabrics, meltblown dry nonwoven fabrics, needle-punched dry nonwoven fabrics, water-jet dry nonwoven fabrics, flash-spun dry nonwoven fabrics, and laminated nonwoven fabrics thereof. Here, there is no particular limitation on the nonwoven fabric constituting the laminated nonwoven fabric; nonwoven fabrics of the same type or different types can be laminated. In addition, nonwoven fabrics manufactured by a papermaking method that can achieve uniform thickness and weight per unit area can also be used as the fabric for protective clothing. Among these, from the viewpoint of excellent productivity, tensile strength, tear strength, dust resistance, and softness, laminated nonwoven fabrics of spunbond dry nonwoven fabrics and meltblown dry nonwoven fabrics are suitable. Specifically, the preferred material is a laminated nonwoven fabric (hereinafter sometimes referred to as SMS nonwoven fabric) formed by sequentially stacking spunbond dry nonwoven fabric, meltblown dry nonwoven fabric and spunbond dry nonwoven fabric.
[0245] Furthermore, the fiber substrate containing the cerium oxide nanoparticles of the present invention can be a laminate formed by stacking a film or metal foil with a nonwoven fabric. For protective clothing using this laminate, the surface (the side opposite to the wearer's side) and the inner surface (the wearer's side) of the protective clothing are preferably made of nonwoven fabric. By using nonwoven fabric on the surface of the protective clothing, the film or metal foil can be protected with nonwoven fabric, and by using nonwoven fabric on the inner surface, a protective clothing with a good skin feel for the wearer can be obtained. The laminate structure of the above-mentioned laminate can be a two-layer laminate structure of nonwoven fabric and film or metal foil, or a four-layer or more laminate structure. Specifically, examples include a laminate structure formed by sequentially stacking spunbond dry nonwoven fabric, a first film, a second film, and spunbond dry nonwoven fabric. In addition, the first film and the second film can be different or the same. Of course, if the required performance is met, it can also be applied to other applications.
[0246] Specific examples of raw materials for the aforementioned nonwoven fabrics are not limited to the types of fibers exemplified above, but among them, from the viewpoint of excellent fabric productivity and hand feel, polyolefin resins are preferred as the main component, and polypropylene is preferred as the main component. Here, the term "main component" refers to the component with the highest content among all the fiber materials constituting the nonwoven fabric. The fiber material of the present invention obtained in this manner, and the fiber products obtained using it as a raw material, are characterized by low colorfastness.
[0247] The fibrous material containing the cerium oxide nanoparticles of the present invention, especially when used as fabric for protective clothing, preferably has a water pressure resistance of 500 mmH2O or more, more preferably 700 mmH2O or more, further preferably 800 mmH2O or more, and particularly more preferably 1000 mmH2O or more. By achieving a water pressure resistance within the aforementioned range, the protective clothing exhibits superior barrier properties. For example, to prevent infections caused by pathogens such as viruses and bacteria, it can inhibit the intrusion of hazardous factors into the inner surface of the protective clothing. Examples of hazardous factors include liquids containing pathogens (e.g., blood, bodily fluids) and airborne suspended particles (e.g., aerosols). Of course, if the required performance is met, it can also be applied to other uses. To achieve the water pressure resistance within the aforementioned range, the preferred fiber substrates are laminated structures consisting of a polypropylene SMS nonwoven fabric, a spunbond dry nonwoven fabric, a membrane, and a spunbond dry nonwoven fabric, as well as a first membrane, a second membrane, and a spunbond dry nonwoven fabric. Furthermore, the first membrane and the second membrane can be different or the same. Because these fiber substrates themselves possess high water pressure resistance, even when the cerium oxide nanoparticles of the present invention are immobilized using the aforementioned method, the water pressure resistance within the aforementioned range can be maintained.
[0248] Furthermore, when an adhesive component is added when immobilizing the cerium oxide nanoparticles of the present invention onto the aforementioned fiber substrate, the content of the adhesive component relative to the entire fiber substrate to which the cerium oxide nanoparticles of the present invention are immobilized is preferably 3% by mass or less, more preferably 2% by mass or less, and even more preferably 1% by mass or less. By keeping the content of the adhesive component within the above range, the reduction in water pressure resistance of the fiber substrate to which the cerium oxide nanoparticles of the present invention are immobilized can be suppressed.
[0249] Regarding the content of cerium oxide nanoparticles relative to the overall fiber material of the present invention, there is no particular limitation as long as they can decompose harmful substances such as viruses and bacteria, but it is preferably 0.01% by mass or more and 60% by mass or less. If the content is less than 0.01% by mass, it cannot exert a sufficient effect. Furthermore, if it is more than 60% by mass, it may sometimes impair the mechanical properties of the fiber, such as strength and durability, or damage the breathability when made into a fabric. Preferably, it is 0.05% by mass or more and 50% by mass or less. More preferably, it is 0.1% by mass or more and 30% by mass or less. Even more preferably, it is 3% by mass or more and 10% by mass or less.
[0250] The fiber material of the present invention obtained by this operation is characterized by exhibiting oxidative decomposition properties against harmful substances such as viruses and bacteria.
[0251] Using the fiber material of the present invention as raw material, fiber products such as masks, protective clothing, filters, mats, chairs, smocks, white coats, curtains, bed sheets, automotive interior materials, and rags can be made.
[0252] Fiber materials and articles thereof containing cerium oxide nanoparticles of the present invention can be used as antiviral fibers. The methods and criteria for evaluating their performance as antiviral fibers are the same as those for evaluating the antiviral properties of the resin compositions and molded articles thereof of the present invention.
[0253] Example
[0254] The present invention will be further illustrated by the following embodiments.
[0255] <Materials and Methods>
[0256] Cerium(III) nitrate hexahydrate, boric acid, and 30% hydrogen peroxide water were obtained from Fujifilm and Hikari Pharmaceutical Co., Ltd.; HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) and imidazole were obtained from Tokyo Chemical Co., Ltd.; and poly(1-vinylimidazolium) was obtained from Maruzen Petrochemical Co., Ltd. Lysine and the commercially available cerium oxide dispersion (796077) used in the comparative example were obtained from Merck. Amiconazole 15 (3kD, 10kD, 30kD) used for purification were purchased from Merck Miracle Co., Ltd.
[0257] Other reagents were purchased from Fujifilm and Hikari Pure Medicine Co., Ltd., Tokyo Kasei Co., Ltd., and Sigmar Aldrich Japan Co., Ltd., and were used directly without special purification.
[0258] In the determination of the hydrodynamic diameter and zeta potential of cerium oxide nanoparticles, the ELSZ-2000ZS zeta potential / particle measurement system of Otsuka Electronics Co., Ltd. was used, and the V-750 UV-Vis-NIR spectrophotometer of Nippon Spectrophotometer Co., Ltd. was used for absorbance measurement.
[0259] The pressure during hydrothermal treatment is derived from the saturated water vapor pressure gauge and temperature.
[0260] (Example 1) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with lysine.
[0261] Except for hydrothermal treatment, the preparation was carried out with reference to Example 4c of Patent Document 1. 4.04 g of L-lysine was dissolved in 500 ml of water and added to 10 g of cerium(III) nitrate hexahydrate. The pH of the mixture was 6.1. 10 ml of 6% hydrogen peroxide solution was further added dropwise. 1 M nitric acid was added to adjust the pH to 2.4, and the reaction was carried out at 40°C for 1 hour. The reaction solution was purified using an ultrafiltration membrane with a molecular weight cutoff of 10 kD to obtain a dispersion (yellow) of cerium oxide nanoparticles stabilized with lysine. This dispersion was transferred to a pressure vessel and subjected to hydrothermal treatment at 120°C (199 kPa) for 20 minutes to obtain a dispersion of cerium oxide nanoparticles stabilized with lysine. The resulting dispersion was transparent.
[0262] (Example 2) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with HEPES
[0263] Except for hydrothermal treatment, the manufacturing process was carried out with reference to Patent Document 2. 0.74 g of HEPES was dissolved in 200 ml of water, and 0.40 g of cerium(III) nitrate hexahydrate was added. After adjusting the pH to 7.0, 4 ml of 1.2% hydrogen peroxide solution was added dropwise, and the reaction was allowed to proceed at room temperature for 1 hour to obtain an orange aqueous solution. The pH was adjusted to 2.3 by adding 1 M nitric acid, and the reaction solution was purified using an ultrafiltration membrane with a molecular weight cutoff of 10 kD to obtain a dispersion (orange) of cerium oxide nanoparticles stabilized by HEPES. This dispersion was transferred to a pressure vessel and subjected to hydrothermal treatment at 120 °C (199 kPa) for 20 minutes to obtain a dispersion of cerium oxide nanoparticles stabilized by HEPES. The resulting dispersion was transparent.
[0264] (Example 3) Preparation of a dispersion of cerium oxide nanoparticles containing imidazole as a stabilizer
[0265] Except for hydrothermal treatment, the manufacturing process was carried out with reference to Patent Document 3. In Example 2, the stabilizer was 0.20 g imidazole, and the reaction was carried out under the same conditions as in Example 2 to obtain a dispersion of cerium oxide nanoparticles with imidazole as the stabilizer. The resulting dispersion was transparent.
[0266] (Example 4) Preparation of a dispersion of cerium oxide nanoparticles containing poly(1-vinylimidazole) as a stabilizer
[0267] Except for hydrothermal treatment, the preparation was carried out with reference to Patent Document 4. A 0.1% by mass aqueous solution of poly(1-vinylimidazole) was used as an aqueous solution of the polymer having an imidazole backbone as a heterocyclic amine backbone. 10 ml of a 10% by mass aqueous solution of cerium(III) nitrate hexahydrate was added to 500 ml of the 0.1% by mass aqueous solution of poly(1-vinylimidazole), and the mixture was stirred at room temperature for 5 minutes. Then, 10 ml of a 1.2% by mass aqueous solution of hydrogen peroxide was added, and the mixture was heated to 60°C and reacted for 1 hour to obtain an orange aqueous solution. The reaction solution was purified using a 30 kD ultrafiltration membrane to obtain a dispersion (orange) of cerium oxide nanoparticles stabilized with poly(1-vinylimidazole). This dispersion was transferred to a pressure vessel and subjected to hydrothermal treatment at 120°C (199 kPa) for 20 minutes to obtain a dispersion of cerium oxide nanoparticles stabilized with imidazole. The resulting dispersion was transparent.
[0268] (Example 5) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with boric acid
[0269] 2.8 g of boric acid was dissolved in 500 ml of water, and the pH was adjusted to 8.0 with sodium hydroxide. 1 g of cerium(III) nitrate hexahydrate was added. 10 ml of 1.2% hydrogen peroxide solution was added dropwise, yielding an orange aqueous solution. 1 M nitric acid was added to adjust the pH to 2.0, and the reaction solution was purified using an ultrafiltration membrane with a molecular weight cutoff of 10 kD, yielding an orange dispersion of cerium oxide nanoparticles stabilized with boric acid. This dispersion was transferred to a pressure vessel and subjected to hydrothermal treatment at 120 °C (199 kPa) for 20 minutes, resulting in a transparent dispersion of cerium oxide nanoparticles stabilized with boric acid.
[0270] (Example 6) Hydrothermal treatment at 105°C
[0271] In Example 5, hydrothermal treatment was performed at 105°C (121 kPa) for 20 minutes. Otherwise, the reaction was carried out under the same conditions as in Example 5 to obtain a dispersion of cerium oxide nanoparticles stabilized with boric acid. The resulting dispersion was transparent.
[0272] (Example 7) Hydrothermal treatment at 135°C
[0273] In Example 5, hydrothermal treatment was performed at 135°C (313 kPa) for 20 minutes. Otherwise, the reaction was carried out under the same conditions as in Example 5 to obtain a dispersion of cerium oxide nanoparticles stabilized with boric acid. The resulting dispersion was transparent.
[0274] (Comparative Example 1) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with lysine.
[0275] In Example 1, hydrothermal treatment was not performed; otherwise, the reaction was carried out under the same conditions as in Example 1 to obtain a dispersion of cerium oxide nanoparticles stabilized with lysine. The resulting dispersion was yellow.
[0276] (Comparative Example 2) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with HEPES
[0277] In Example 2, hydrothermal treatment was not performed; otherwise, the reaction was carried out under the same conditions as in Example 2, resulting in a dispersion of cerium oxide nanoparticles stabilized with HEPES. The resulting dispersion was orange.
[0278] (Comparative Example 3) Preparation of a dispersion of cerium oxide nanoparticles containing imidazole as a stabilizer
[0279] In Example 3, hydrothermal treatment was not performed; otherwise, the reaction was carried out under the same conditions as in Example 3, resulting in a dispersion of cerium oxide nanoparticles stabilized with imidazole. The resulting dispersion was orange.
[0280] (Comparative Example 4) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with poly(1-vinylimidazole)
[0281] In Example 4, hydrothermal treatment was not performed; otherwise, the reaction was carried out under the same conditions as in Example 4, resulting in a dispersion of cerium oxide nanoparticles stabilized with poly(1-vinylimidazole). The resulting dispersion was orange in color.
[0282] (Comparative Example 5) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with boric acid
[0283] In Example 5, instead of hydrothermal treatment, the mixture was heated to 100°C (101 kPa) by reflux for 2 hours. Otherwise, the reaction was carried out under the same conditions as in Example 5, yielding a dispersion of cerium oxide nanoparticles stabilized with boric acid. The resulting dispersion was orange in color.
[0284] (Comparative Example 6) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with citric acid
[0285] The preparation was carried out with reference to Non-Patent Literature 1. 5 ml of a 1M cerium(III) chloride aqueous solution and 5 ml of a 1M citric acid aqueous solution were mixed and added dropwise to 50 ml of a 3M ammonia aqueous solution. The mixture was reacted at 50°C for 24 hours to obtain a brown aqueous solution. The reaction solution was purified using a 3kD ultrafiltration membrane to obtain a dispersion of cerium oxide nanoparticles stabilized with citric acid. The resulting dispersion was brown. This dispersion was transferred to a pressure vessel and subjected to hydrothermal treatment at 120°C (199kPa) for 20 minutes. The resulting dispersion was brown.
[0286] (Comparative Example 7) Preparation of a dispersion containing cerium oxide nanoparticles stabilized with dextran
[0287] The preparation was carried out with reference to Non-Patent Literature 2. 1 ml of 1 M cerium(III) nitrate was mixed with 2 ml of 0.1 M dextran (10 kD), and then added dropwise to 6 ml of a 30% ammonia solution. The mixture was allowed to react at room temperature for 24 hours, yielding a brown aqueous solution. The reaction solution was purified using a 10 kD ultrafiltration membrane to obtain a dispersion of cerium oxide nanoparticles stabilized with dextran. The resulting dispersion was brown. This dispersion was transferred to a pressure vessel and subjected to hydrothermal treatment at 120°C (199 kPa) for 20 minutes. The resulting dispersion was brown.
[0288] (Example 8) Determination of the hydrodynamic diameter of a dispersion containing cerium oxide nanoparticles
[0289] The hydrodynamic diameters of the cerium oxide nanoparticles produced in Examples 1–7 were determined by dynamic light scattering (DLS). Water was used as the solvent for the measurements, and the average particle size of the hydrodynamic diameter was obtained by conversion of the number of particles. The obtained values are shown in Table 1.
[0290] The average particle size ranged from 8.0 to 40.3 nm, confirming that they were all nanoparticles.
[0291] (Table 1)
[0292]
[0293] (Example 9) Determination of APHA of a dispersion containing cerium oxide nanoparticles
[0294] The cerium oxide nanoparticles produced in Examples 1-7 were prepared into a 1% by mass dispersion, and the APHA was determined. The results are shown in Table 2.
[0295] The APHA value was 131–192, confirming that all nanoparticles exhibited low colorimetric properties.
[0296] (Table 2)
[0297]
[0298] (Comparative Example 8) Determination of APHA of a dispersion containing cerium oxide nanoparticles
[0299] The APHA of cerium oxide nanoparticles produced in Comparative Examples 1-7 and a commercially available aqueous dispersion of cerium oxide (Merck Co., 796077) as Reference Example 1 were measured. The results are shown in Table 3.
[0300] An APHA value of 402 or higher confirms that any nanoparticle possesses high colorability.
[0301] (Table 3)
[0302]
[0303] (Example 10) Determination of Zeta potential of a dispersion containing cerium oxide nanoparticles
[0304] The zeta potentials of the cerium oxide nanoparticles prepared in Examples 1–7 were determined. Water was used as the solvent for the measurements, and the pH of each sample was adjusted to 7 using nitric acid or sodium hydroxide. The obtained values are shown in Table 4.
[0305] The zeta potential ranges from +37.4 to 45.8 mV, confirming that any nanoparticle possesses a high positive charge.
[0306] (Table 4)
[0307]
[0308] (Comparative Example 9) Determination of Zeta potential of dispersions containing cerium oxide nanoparticles
[0309] The zeta potentials of the cerium oxide nanoparticles prepared in Comparative Examples 6 and 7 were determined. Water was used as the solvent for the measurements, and the pH of each sample was adjusted to 7 using nitric acid or sodium hydroxide. The obtained values are shown in Table 5.
[0310] The zeta potentials were -31.6 and +5.0 mV, respectively, confirming that any nanoparticle is either negatively charged or weakly positively charged.
[0311] (Table 5)
[0312]
[0313] (Example 11) XAFS analysis of a dispersion containing cerium oxide nanoparticles
[0314] The dispersion of cerium oxide nanoparticles of the present invention, prepared in Examples 1-5, was adjusted to a concentration of 10 mg / ml and irradiated with X-rays. The absorption was measured to determine the X-ray absorption fine structure spectrum. The measurement conditions were as follows: the experimental facility was the Photon Factory BL12C at the High Energy Accelerator Research Organization; the spectrometer was a Si(111)2 crystal spectrometer; the absorption end was a Ce L3 absorption end; the detection method was transmission; and the detector was an ionization chamber.
[0315] The CeL3-terminal XANES spectra of the cerium oxide nanoparticles produced in Examples 1-5 are shown in [the figures]. Figures 3-7 The vertical axis was set by setting the absorption end (E0) at 5724.4 eV, setting the average absorption value in the range of E0 to -150 to -30 eV to 0, and setting the average absorption value in the range of E0 to +150 to +400 eV to 1, thus obtaining the ratio.
[0316] The results clearly show that the nanoparticles of Example 1 have maximum absorption at 5729.598 eV and 5736.424 eV, the nanoparticles of Example 2 have maximum absorption at 5729.588 eV and 5736.424 eV, the nanoparticles of Example 3 have maximum absorption at 5729.588 eV and 5736.263 eV, the nanoparticles of Example 4 have maximum absorption at 5729.433 eV and 5736.424 eV, the nanoparticles of Example 5 have maximum absorption at 5729.598 eV and 5736.287 eV, and the nanoparticles of Examples 1 to 5 have maximum absorption in the range of greater than 5729 eV and less than 5731 eV, and greater than 5735 eV and less than 5739 eV.
[0317] (Comparative Example 10) XAFS analysis of a dispersion containing cerium oxide nanoparticles
[0318] As a comparison with Example 11, the cerium oxide nanoparticles of Comparative Examples 1 to 5 were measured. The CeL3-terminal XANES spectra of the cerium oxide nanoparticles produced in Comparative Examples 1 to 5 are shown below. Figures 3-7 middle.
[0319] The results show that the nanoparticles of Comparative Example 1 exhibit maximum absorption at 5727.705 eV and 5736.964 eV, the nanoparticles of Comparative Example 2 exhibit maximum absorption at 5727.990 eV and 5736.570 eV, the nanoparticles of Comparative Example 3 exhibit maximum absorption at 5728.003 eV and 5736.263 eV, the nanoparticles of Comparative Example 4 exhibit maximum absorption at 5728.003 eV and 5736.582 eV, the nanoparticles of Comparative Example 5 exhibit maximum absorption at 5727.974 eV and 5736.964 eV, and the nanoparticles of Comparative Examples 1 to 5 exhibit maximum absorption between 5735 and 5739 eV, but do not exhibit maximum absorption in the range greater than 5729 eV and less than 5731 eV.
[0320] (Example 12) Using XPS Ce 4+ With Ce 3+ Determination of molar ratio
[0321] The Ce content of the cerium oxide nanoparticles obtained in Examples 1–7 was determined by X-ray photoelectron spectroscopy (XPS). 4+ With Ce 3+ The molar ratio. In the determination, the excitation X-rays are made monoocheomatic AlK. α1,2 The X-rays (1486.6 eV) were used to create an X-ray diameter of 200 μm and a photoelectron emission angle of 45°. The resulting spectrum was used to make Ce3d 5 / 2 Ce below 4+ The main peak was corrected for the horizontal axis by setting it to 881.8 eV. During the determination, the cerium oxide nanoparticles produced in Examples 1-7 were used as powders whose dispersions were purified and then freeze-dried. The obtained values are shown in Table 6.
[0322] The results show that the cerium oxide nanoparticles produced in Examples 1-7 have a high Ce content. 4+ With Ce 3+ The molar ratio is 65:35 to 95:5, Ce 4+ The proportion is high.
[0323] Furthermore, it is known that the nanoparticles of the present invention, which improve colorability in combination with those of Example 11, exhibit extremely high absorption in the Ce L3-terminal XANES spectrum obtained by X-ray absorption fine structure spectroscopy in the range greater than 5729 eV and less than 5731 eV and between 5735 eV and less than 5739 eV, and Ce 4+ With Ce 3+ The molar ratio is 40:60 to 100:0.
[0324] (Table 6)
[0325]
[0326] (Comparative Example 11) Using XPS's Ce 4+ With Ce 3+ Determination of molar ratio
[0327] The cerium oxide nanoparticles obtained in Comparative Examples 4-7 and the commercially available product (Merck Co., 796077) used as Reference Example 1 were measured by X-ray photoelectron spectroscopy (XPS). 4+ With Ce 3+ The molar ratio was determined under the same conditions as in Example 11. The values obtained are shown in Table 7.
[0328] The results show that the cerium oxide nanoparticles of Comparative Examples 6, 7, and the commercially available product (Melk, 796077) have a higher Ce content. 4+ With Ce 3+ The molar ratio is 7:93 to 39:61, Ce 4+ The proportion is low.
[0329] Furthermore, as can be seen from these results and Comparative Example 10, the cerium oxide nanoparticles of Comparative Examples 4 and 5, which exhibit coloring properties, although Ce 4+ With Ce 3+ The molar ratio is 40:60 to 100:0. However, in the Ce L3 end XANES spectrum obtained by X-ray absorption fine structure spectroscopy, although there is a maximum absorption above 5735 eV and below 5739 eV, there is no maximum absorption in the range of greater than 5729 eV and below 5731 eV.
[0330] (Table 7)
[0331]
[0332] (Example 13) XRD analysis of cerium oxide nanoparticles
[0333] The dispersions of cerium oxide nanoparticles of the present invention, prepared in Examples 1-5 at a concentration of 100 mg / ml, were measured by X-ray diffraction (XRD). The measurement conditions were as follows: CuKα light source, output of 40 kV and 40 mA, LynxEye detector, and measurement range of 2θ = 5–80°. The obtained XRD spectra are shown below. Figures 8-12 In Table 8, the ratio of the peak intensity at 27°–29° to the peak intensity at 46°–48° is shown.
[0334] The results clearly show that the nanoparticles of Example 1 have diffraction peaks at 2θ = 28.360°, 32.899°, 47.400°, and 56.119°; the nanoparticles of Example 2 have diffraction peaks at 2θ = 28.360°, 32.761°, 47.400°, and 56.340°; the nanoparticles of Example 3 have diffraction peaks at 2θ = 28.400°, 32.960°, 47.240°, and 56.100°; the nanoparticles of Example 4 have diffraction peaks at 2θ = 28.440°, 32.979°, 47.260°, and 56.140°; and the nanoparticles of Example 5 have diffraction peaks at 2θ = 28.380°, 32.840°, 47.241°, and 55.861°. The results show that the cerium oxide nanoparticles of the present invention have diffraction peaks in the XRD spectrum at Bragg angles 2θ of 27°–29°, 31°–33°, 46°–48°, and 55°–57°, respectively.
[0335] Furthermore, it is known that in the obtained XRD spectra of the nanoparticles of Examples 1 to 5, the ratio of the peak intensity at 27° to 29° to the peak intensity at 46° to 48° is 0.89 to 1.6.
[0336] Therefore, it can be seen that the nanoparticles with improved colorability of the present invention have diffraction peaks in the XRD spectrum at Bragg angles (2θ) of 27° to 29°, 31° to 33°, 46° to 48°, and 55° to 57°, and the ratio of the peak intensity at 27° to 29° to the peak intensity at 46° to 48° is less than 1.8.
[0337] (Table 8)
[0338]
[0339] (Comparative Example 12) XRD Analysis of Cerium Oxide Nanoparticles
[0340] As a comparison with Example 13, the cerium oxide nanoparticles of Comparative Examples 1-7 and the commercially available product (Merck, 796077) as Reference Example 1 were measured. The obtained XRD spectra are shown below. Figures 13-20 The results show that the nanoparticles of Comparative Examples 1-5 have different diffraction patterns than those of the nanoparticles of Examples 1-5.
[0341] Furthermore, the ratios of peak intensities at 27°–29° to peak intensities at 46°–48°, calculated from the above measurements for Comparative Examples 6 and 7 and the commercially available product (Melk, 796077), are shown in Table 9. Additionally, regarding the literature (US2013 / 0273659)... Figure 1The ratio of the peak intensity at 27°–29° to the peak intensity at 46°–48° for the cerium oxide nanoparticles described herein, calculated from the published spectra, is shown in Table 9.
[0342] The results show that the ratio of the peak intensity at 27°–29° to the peak intensity at 46°–48° of these nanoparticles is greater than 1.9.
[0343] (Table 9)
[0344]
[0345] (Example 14) Virus inactivation test
[0346] In 0.9 ml of a dispersion of cerium oxide nanoparticles prepared in Examples 1-5, adjusted to a concentration of 0.56 mg / ml, 0.1 ml of viral fluid (influenza virus, ATCC, VR-1679, Influenza Avirus (H3N2)) was mixed and allowed to react for 1 hour. Then, PBS (phosphate-buffered saline) was added as a stop solution to cease the action on the virus. The viral infection titer was determined using this solution as the stock solution for viral infection titer assay via plaque assay. The logarithmic decrease in infection titer relative to the infection titer before the reaction with the cerium oxide nanoparticles is shown in Table 10 as the antiviral activity value.
[0347] Based on these results, the antiviral activity values of the cerium oxide nanoparticles in Examples 1-5 were 2.7-4.5, confirming their antiviral activity.
[0348] (Table 10)
[0349]
[0350] (Comparative Example 13) Virus inactivation test
[0351] Cerium oxide nanoparticles prepared in Comparative Examples 1-5 were used, and the reaction was carried out under the same conditions as in Example 14, and a virus inactivation test was performed. The obtained values are shown in Table 11.
[0352] The results show that, without hydrothermal treatment, the antiviral activity of cerium oxide nanoparticles is 1.9–3.0. Although cerium oxide nanoparticles have antiviral activity, their activity is lower compared to those of hydrothermally treated particles.
[0353] (Table 11)
[0354]
[0355] (Example 15) Antibacterial test
[0356] Precultured *E. coli* in LB medium was suspended in a bacterial culture preparation solution (0.1% tryptone, 0.85% NaCl) to prepare 10... 8 CFU / ml bacterial suspension. 0.1 ml of this bacterial suspension was mixed with 0.9 ml of a dispersion obtained by adjusting the concentration of cerium oxide nanoparticles prepared in Examples 1-5 to 0.11 mg / ml, and allowed to stand at room temperature for one hour. Then, a series of dilutions were prepared using this mixture as the stock solution, inoculated onto LB agar medium, and the colony count was determined. The logarithmic decrease in colony count relative to the number of colonies before the application of cerium oxide nanoparticles is shown in Table 10 as the antibacterial activity value.
[0357] Based on these results, the antibacterial activity values of the cerium oxide nanoparticles in Examples 1-5 were 2.0-3.7, confirming the antibacterial activity.
[0358] (Comparative Example 14) Antibacterial Test
[0359] Cerium oxide nanoparticles prepared in Comparative Examples 1-5 were used, and the reaction was carried out under the same conditions as in Example 15, and an antibacterial test was conducted. The obtained values are shown in Table 11.
[0360] The results show that, without hydrothermal treatment, the antibacterial activity of cerium oxide nanoparticles is 1.4–2.2. Although cerium oxide nanoparticles have antibacterial activity, their activity is lower than that of hydrothermally treated particles.
[0361] (Example 16)
[0362] 97 parts by weight of ABS resin granules (Tore Manufacturing, General Purpose Resin "Toyorak (Registered Trademark)" 100322), 3 parts by weight of cerium oxide nanoparticles manufactured in Example 5, and 0.5 parts by weight of pure water as a spreading agent were mixed. The mixture was stirred at 23°C for 60 seconds using a Henschel mixer. The resulting mixture was then melt-blended at an extrusion temperature of 230°C using a 40mm φ extruder with a vent, and granulated by strip extrusion to obtain a resin composition. Next, the obtained granules were used to form 3mm thick square plates using an injection molding machine set to a barrel temperature of 230°C. The hue of the obtained square plates was determined using a color computer manufactured by Suga Testing Equipment Co., Ltd., and the YI value was measured as yellowness (YI). Furthermore, a virus inactivation test was conducted using the following method: A 50mm × 50mm × 1mm square plate of the molded resin composition was placed in a humidified petri dish. 0.4 ml of viral solution (feline calicivirus, F-9, ATCC, VR-782, replacing norovirus) was added dropwise to the molded resin composition, and the mixture was allowed to react for 24 hours on a 4 cm × 4 cm membrane (PP). Then, PBS was added as a stop solution to cease the reaction with the virus, and the virus on the molded resin composition was washed away and recovered. This recovered solution was used as the stock solution for the virus infection titer assay and passed through TCID. 50 The infection titer was determined by a method.
[0363] The antiviral activity was evaluated by comparing the commonly used logarithmic value of the viral infection titer obtained when the molded article using the resin composition of the present invention was tested with the commonly used logarithmic value of the viral infection titer obtained when the resin composition using cerium oxide nanoparticles (blank) was tested. A higher viral inactivation index indicates higher antiviral activity. Specifically, a logarithmic decrease in infection titer (viral inactivation index) of 2.0 or higher was considered to indicate effective antiviral performance.
[0364] The evaluation results are shown in Table 12.
[0365] (Example 17)
[0366] 97 parts by weight of ABS resin particles (Tore, a registered trademark "Toyorak Parrel" TP10, a durable antistatic resin), 3 parts by weight of cerium oxide nanoparticles produced in Example 5, and 0.5 parts by weight of pure water as a spreading agent were mixed. Otherwise, a resin composition was obtained by the same method as in Example 16. The evaluation results are shown in Table 12.
[0367] (Example 18)
[0368] 90 parts by weight of ABS resin particles (Tore-made, a persistent antistatic resin "Toyorak Parrel (registered trademark)" TP10), 10 parts by weight of cerium oxide nanoparticles manufactured in Example 5, and 0.5 parts by weight of pure water as a spreading agent were mixed. Otherwise, a resin composition was obtained by the same method as in Example 16. The evaluation results are shown in Table 12.
[0369] (Example 19)
[0370] 97 parts by weight of nylon 6 resin granules (made by Tore) and 3 parts by weight of cerium oxide nanoparticles manufactured in Example 5 were mixed and granulated by melt mixing in a 40 mm φ extruder with a vent at an extrusion temperature of 250°C and extruded in strips to obtain a resin composition. Next, the obtained granules were used to form 3 mm thick square plates using an injection molding machine set to a barrel temperature of 250°C. The hue of the obtained square plates was measured using a color computer manufactured by Suga Testing Equipment Co., Ltd., and the YI value was determined as yellowness (YI). Furthermore, the antiviral properties of the obtained resin composition were measured using the above method. The evaluation results are shown in Table 12.
[0371] (Example 20)
[0372] 90 parts by weight of nylon 6 resin particles (made by Higashi Rei) and 10 parts by weight of cerium oxide nanoparticles manufactured in Example 5 were mixed together. Otherwise, a resin composition was obtained by the same method as in Example 19. The evaluation results are shown in Table 12.
[0373] (Example 21)
[0374] 97 parts by weight of polybutylene terephthalate (PBT) resin particles (manufactured by Higashi Re) and 3 parts by weight of cerium oxide nanoparticles manufactured in Example 5 were mixed and granulated by melt mixing and extrusion at an extrusion temperature of 250°C using a 40mm φ extruder with a vent, to obtain a resin composition. Next, the obtained particles were used to form 3mm thick square plates using an injection molding machine set to a barrel temperature of 250°C. The hue of the obtained square plates was measured using a color computer manufactured by Suga Testing Equipment Co., Ltd., and the YI value was determined as yellowness (YI). Furthermore, the antiviral properties of the obtained resin composition were measured using the above method. The evaluation results are shown in Table 12.
[0375] (Example 22)
[0376] 90 parts by weight of polybutylene terephthalate (PBT) resin particles (made by Higashi Rei) and 10 parts by weight of cerium oxide nanoparticles manufactured in Example 5 were mixed together. Otherwise, a resin composition was obtained by the same method as in Example 21. The evaluation results are shown in Table 12.
[0377] (Comparative Example 15)
[0378] 97 parts by weight of ABS resin particles (Tore Manufacturing, General Purpose Resin "Toyorak (Registered Trademark)" 100322), 3 parts by weight of cerium oxide nanoparticles manufactured in Comparative Example 5, and 0.5 parts by weight of pure water as a spreading agent were mixed. Otherwise, a resin composition was obtained by the same method as in Example 16. The evaluation results are shown in Table 12.
[0379] (Comparative Example 16)
[0380] 97 parts by weight of ABS resin particles (Tore, a registered trademark for a durable antistatic resin called "Toyorak Parrel"), 3 parts by weight of cerium oxide nanoparticles produced in Comparative Example 5, and 0.5 parts by weight of pure water as a spreading agent were mixed. Otherwise, a resin composition was obtained by the same method as in Example 16. The evaluation results are shown in Table 12.
[0381] (Comparative Example 17)
[0382] 97 parts by weight of nylon 6 resin particles (made by Higashi Rei) and 3 parts by weight of cerium oxide nanoparticles manufactured in Comparative Example 5 were mixed together. Otherwise, a resin composition was obtained by the same method as in Example 19. The evaluation results are shown in Table 12.
[0383] (Comparative Example 18)
[0384] 97 parts by weight of polybutylene terephthalate resin particles (made by Tore) and 3 parts by weight of cerium oxide nanoparticles manufactured in Comparative Example 5 were mixed together. Otherwise, a resin composition was obtained by the same method as in Example 21. The evaluation results are shown in Table 12.
[0385] (Table 12)
[0386] base resin hydrothermal treatment Antiviral activity YI Example 16 ABS have 2 2.2 Example 17 ABS have 2.2 3.2 Example 18 ABS have 2.7 3.8 Example 19 Nylon 6 have 2 3 Example 20 Nylon 6 have 2.3 4.8 Example 21 PBT have 2 2.1 Example 22 PBT have 2.2 3.4 Comparative Example 15 ABS none 1.8 18.8 Comparative Example 16 ABS none 2 23 Comparative Example 17 Nylon 6 none 1.7 33.1 Comparative Example 18 PBT none 1.5 21.7
[0387] The resin compositions of Examples 16 to 22, compared with the resin compositions of Comparative Examples 15 to 18, were found to have high antiviral activity and excellent color tone.
[0388] (Example 23)
[0389] Polypropylene spunbond nonwoven fabric (made by Tore) was cut into 5cm squares and immersed for 1 hour in an aqueous dispersion containing 1 part by weight of cerium oxide nanoparticles produced in Example 5, 1 part by weight of self-crosslinking acrylic adhesive (Boncote AN-1170, made by DIC), and 98 parts by weight of water. Then, after gentle pressing, it was dried in an oven at 130°C for 2 hours. The coloring of the resulting nonwoven fabric immobilized with cerium oxide nanoparticles was visually confirmed. Furthermore, the antiviral properties of the resulting nonwoven fabric were measured using the above method. The evaluation results are shown in Table 13.
[0390] (Example 24)
[0391] Instead of the aqueous dispersion of Example 23, an aqueous dispersion containing 5 parts by mass of cerium oxide nanoparticles manufactured in Example 5, 5 parts by mass of a self-crosslinking acrylic adhesive (Boncote AN-1170, manufactured by DIC), and 90 parts by mass of water was used. Except for this, a nonwoven fabric immobilized with cerium oxide nanoparticles was obtained using the same method as in Example 23. The evaluation results of coloring and antiviral properties are shown in Table 13.
[0392] (Example 25)
[0393] Instead of polypropylene spunbond nonwoven fabric (made by Higashi Re), rayon nonwoven fabric (made by Claffrex) was used. Except for this, a nonwoven fabric with immobilized cerium oxide nanoparticles was obtained by the same method as in Example 23. The evaluation results of coloring and antiviral properties are shown in Table 13.
[0394] (Example 26)
[0395] Instead of polypropylene spunbond nonwoven fabric (made by Higashi Re), rayon nonwoven fabric (made by Claffrex) was used. Instead of the aqueous dispersion of Example 23, an aqueous dispersion containing 5 parts by mass of cerium oxide nanoparticles manufactured in Example 5, 5 parts by mass of self-crosslinking acrylic adhesive (Boncote AN-1170, made by DIC), and 90 parts by mass of water was used. Except for this, a nonwoven fabric immobilized with cerium oxide nanoparticles was obtained by the same method as in Example 23. The evaluation results of coloring and antiviral properties are shown in Table 13.
[0396] (Comparative Example 19)
[0397] Instead of the aqueous dispersion of Example 23, an aqueous dispersion containing 1 part by mass of cerium oxide nanoparticles manufactured in Comparative Example 5, 1 part by mass of self-crosslinking acrylic adhesive (Boncote AN-1170, manufactured by DIC), and 98 parts by mass of water was used. Except for this, a nonwoven fabric immobilized with cerium oxide nanoparticles was obtained by the same method as in Example 23. The evaluation results of coloring and antiviral properties are shown in Table 13.
[0398] (Comparative Example 20)
[0399] Instead of the aqueous dispersion of Example 23, an aqueous dispersion containing 5 parts by mass of cerium oxide nanoparticles manufactured in Comparative Example 5, 5 parts by mass of a self-crosslinking acrylic adhesive (Boncote AN-1170, manufactured by DIC), and 90 parts by mass of water was used. Except for this, a nonwoven fabric immobilized with cerium oxide nanoparticles was obtained by the same method as in Example 23. The evaluation results of coloring and antiviral properties are shown in Table 13.
[0400] (Comparative Example 21)
[0401] Instead of polypropylene spunbond nonwoven fabric (manufactured by Higashi Re), rayon nonwoven fabric (manufactured by Claffrex) was used. Instead of the aqueous dispersion of Example 23, an aqueous dispersion containing 1 part by mass of cerium oxide nanoparticles manufactured in Comparative Example 5, 1 part by mass of self-crosslinking acrylic adhesive (Bonccott AN-1170, manufactured by DIC), and 98 parts by mass of water was used. Except for this, a nonwoven fabric immobilized with cerium oxide nanoparticles was obtained by the same method as in Example 23. The evaluation results of coloring and antiviral properties are shown in Table 13.
[0402] (Comparative Example 22)
[0403] Instead of polypropylene spunbond nonwoven fabric (manufactured by Higashi Re), rayon nonwoven fabric (manufactured by Claffrex) was used. Instead of the aqueous dispersion of Example 23, an aqueous dispersion containing 5 parts by mass of cerium oxide nanoparticles manufactured in Comparative Example 5, 5 parts by mass of self-crosslinking acrylic adhesive (Bonccott AN-1170, manufactured by DIC), and 90 parts by mass of water was used. Except for this, a nonwoven fabric immobilized with cerium oxide nanoparticles was obtained by the same method as in Example 23. The evaluation results of coloring and antiviral properties are shown in Table 13.
[0404] The fiber materials of Examples 23 to 26, compared with the fiber materials of Comparative Examples 19 to 22, were found to have high antiviral activity and no coloring.
[0405] (Table 13)
[0406] Fiber substrate hydrothermal treatment Antiviral activity Coloring Example 23 polypropylene have 2.7 none Example 24 polypropylene have >3.0 none Example 25 nylon have 2.5 none Example 26 nylon have >3.0 none Comparative Example 19 polypropylene none 1.2 have Comparative Example 20 polypropylene none 1.5 have Comparative Example 21 nylon none 1.1 have Comparative Example 22 nylon none 1.6 have
[0407] (Example 27)
[0408] The unit area weight is 65g / m² 2 Polypropylene SMS nonwoven fabric (made by Tore) was cut into A4 size (298mm × 210mm). Next, an aqueous dispersion containing 2.5 parts by weight of cerium oxide nanoparticles produced in Example 5, 1.5 parts by weight of a self-crosslinking acrylic adhesive (Bonccott AN-1170, manufactured by DIC), and 96.0 parts by weight of water was dip-nip shaped using an Oemmasin P-215 press at a barrel pressure of 0.2 MPa and a speed of 2.0 m / min. It was then dried for 2 minutes using a pin-plate tenter frame (made by Hanayama Kogyo). The coloring of the resulting nonwoven fabric immobilized with cerium oxide nanoparticles was visually confirmed. Furthermore, a virus inactivation test was conducted using the following method: The obtained nonwoven fabric was cut into 50mm × 50mm pieces and placed in a humidified culture dish. 0.4 ml of viral solution (feline calicivirus, F-9, ATCC, VR-782, replacing norovirus) was added to the obtained nonwoven fabric, and it was allowed to react for 2 hours on a 4 cm × 4 cm membrane (PP). Then, PBS was added as a stop solution to stop the reaction with the virus, and the virus was washed off the obtained nonwoven fabric and recovered. This recovered solution was used as the stock solution for the virus infection titer assay via TCID. 50 The infection titer was determined by a method.
[0409] The antiviral activity was evaluated by comparing the commonly used logarithmic value of the viral infection titer obtained from the experiment using the obtained nonwoven fabric with the commonly used logarithmic value of the viral infection titer obtained from the experiment using SMS nonwoven fabric (blank) without cerium oxide nanoparticles. A higher viral inactivation index indicates higher antiviral activity. Specifically, a logarithmic reduction in infection titer (viral inactivation index) of 2.0 or higher was considered as effective antiviral performance.
[0410] The water pressure resistance of the obtained nonwoven fabric was measured according to JIS L1092 A method (low water pressure method) using the TEXTEST FX-3000-IV "High Pressure Tester". The evaluation results are shown in Table 14.
[0411] (Example 28)
[0412] Instead of the aqueous dispersion of Example 27, an aqueous dispersion containing 3.3 parts by mass of cerium oxide nanoparticles manufactured in Example 5, 2.0 parts by mass of a self-crosslinking acrylic adhesive (Boncote AN-1170, manufactured by DIC), and 94.7 parts by mass of water was used. Except for this, a nonwoven fabric immobilized with cerium oxide nanoparticles was obtained using the same method as in Example 27. Coloring, antiviral properties, and water pressure resistance were evaluated using the same method as in Example 27, and the evaluation results are shown in Table 14.
[0413] The fiber materials of Examples 27 and 28 were confirmed to have high antiviral activity and water pressure resistance, and were not colored.
[0414] (Table 14)
[0415]
Claims
1. A type of cerium oxide nanoparticle, characterized in that, It is a nanoparticle containing basic amino acids, alicyclic amines, aromatic heterocyclic compounds containing nitrogen atoms in the ring structure, polymers with heterocyclic amine skeletons, or cerium oxide as a boron compound stabilizer, with an APHA of less than 400 in a 1% by mass dispersion.
2. The cerium oxide nanoparticles according to claim 1 have a zeta potential of +10mV or higher at pH 7.
3. The cerium oxide nanoparticles according to claim 1, wherein, Ce 4+ With Ce 3+ The molar ratio is 40:60 to 100:
0.
4. A type of cerium oxide nanoparticle, comprising a basic amino acid, an alicyclic amine, an aromatic heterocyclic compound containing a nitrogen atom within its ring structure, a polymer having a heterocyclic amine backbone, or a boron compound as a stabilizer, exhibiting maximum absorption in the Ce L3-terminal XANES spectrum obtained by X-ray absorption microstructure spectroscopy in the range greater than 5729 eV and below 5731 eV and between 5735 and 5739 eV, and Ce… 4+ With Ce 3+ The molar ratio is 40:60 to 100:
0.
5. A cerium oxide nanoparticle, comprising a basic amino acid, an alicyclic amine, an aromatic heterocyclic compound containing a nitrogen atom in the ring structure, a polymer having a heterocyclic amine skeleton, or a boron compound as a stabilizer, wherein the cerium oxide nanoparticle has diffraction peaks at Bragg angles 2θ of 27°–29°, 31°–33°, 46°–48°, and 55°–57° in XRD spectra, and the ratio of the peak intensity at 27°–29° to the peak intensity at 46°–48° is less than 1.
8.
6. The cerium oxide nanoparticles according to any one of claims 1 to 5, wherein the alicyclic amine is an alicyclic amine represented by the following general formula (I), In equation (I), X represents NR. 2 O, S, R 1 and R 2 Represents hydrogen atoms, alkyl groups having 1 to 4 carbon atoms, hydroxyalkyl groups having 1 to 4 carbon atoms, aminoalkyl groups having 1 to 4 carbon atoms, and sulfonic acid alkyl groups having 1 to 4 carbon atoms; R 1 and R 2 They can be the same or different.
7. The cerium oxide nanoparticles according to any one of claims 1 to 5, wherein the aromatic heterocyclic compound containing nitrogen atoms in the ring structure does not have substituents, or has at least one substituent selected from methyl, ethyl, amino, aminomethyl, monomethylamino, dimethylamino, and cyano, and is an aromatic heterocyclic compound containing 2 to 8 carbon atoms and 1 to 4 nitrogen atoms in the ring structure.
8. The cerium oxide nanoparticles according to any one of claims 1 to 5, wherein the polymer having a heterocyclic amine backbone is a vinyl polymer or polyamide having a heterocyclic amine backbone.
9. The cerium oxide nanoparticles according to any one of claims 1 to 5, wherein the boron compound is a boron compound represented by the following general formula (II), BR n (OR’) 3-n (II) In formula (II), n is an integer from 0 to 2, R represents any one of alkyl, phenyl or tolyl with 1 to 4 carbon atoms, and R' represents any one of hydrogen, alkyl, phenyl or tolyl with 1 to 4 carbon atoms; when there are multiple R or R', they can be the same or different.
10. The cerium oxide nanoparticles according to any one of claims 1 to 5, characterized in that, The particle size is 1–300 nm.
11. A dispersion comprising cerium oxide nanoparticles according to any one of claims 1 to 10.
12. An antiviral agent comprising cerium oxide nanoparticles according to any one of claims 1 to 10 or the dispersion according to claim 11.
13. An antibacterial agent comprising cerium oxide nanoparticles according to any one of claims 1 to 10 or the dispersion according to claim 11.
14. A resin composition comprising cerium oxide nanoparticles according to any one of claims 1 to 10.
15. A resin article wherein the resin composition of claim 14 is used.
16. The resin article according to claim 15, wherein the resin article is selected from automotive interior materials, electrical product housings, hanging handles, armrests, door handles, and partitions.
17. A fiber material comprising cerium oxide nanoparticles according to any one of claims 1 to 10.
18. The fiber material according to claim 17, characterized in that, It can withstand water pressure of 500 mmH2O or higher.
19. A fiber article wherein the fiber material of claim 17 or 18 is used.
20. The fiber product according to claim 19, wherein the fiber product is selected from masks, protective clothing, filters, mats, chairs, gowns, lab coats, curtains, bed sheets, automotive interior materials, and rags.
21. A method for manufacturing cerium oxide nanoparticles according to any one of claims 1 to 10, comprising the following steps: Step a) The step of adding an oxidizing agent to a solution containing basic amino acids, alicyclic amines, aromatic heterocyclic compounds containing nitrogen atoms in their ring structure, polymers having a heterocyclic amine backbone, or boron compounds and containing cerium(III) ions. Step b) is the process of hydrothermally treating the solution obtained in step a). The hydrothermal treatment is carried out using water at a temperature above 100°C and a pressure above 101 kPa (i.e., 1 atmosphere).
22. The method for manufacturing cerium oxide nanoparticles according to claim 21, wherein the APHA of a 1% by mass dispersion of the cerium oxide nanoparticles is 400 or less.
Citation Information
Patent Citations
Gel-free colloidal abrasive polishing composition and associated method
JP2003183631A
Nanoparticles of cerium and amino acids
US20130273659A1
Cerium oxide nanoparticles, method for analyzing nucleic acid, method for analyzing polypeptide, method for manufacturing cerium oxide nanoparticles, oxidizing agent, antioxidant, antifungal agent, and antiviral agent
WO2020129963A1
Cerium oxide nanoparticles, dispersion, oxidizing agent, antioxidant, and method for manufacturing cerium oxide nanoparticles
WO2021132628A1
Cerium oxide nanoparticles, dispersion, oxidant, antioxidant and method for producing cerium oxide nanoparticles
WO2021132643A1
